Perovskite solar cell with interface layer

The use of a metallocene-based interface layer addresses the stability and efficiency issues in perovskite solar cells by enhancing charge transport and reducing defects, improving performance and longevity.

CN119138121APending Publication Date: 2024-12-13IMPERIAL COLLEGE INNVOATIONS LTD +1

Patent Information

Application Number
CN202380035077.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-20
Filing Date
2023-04-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing perovskite solar cells face issues with short lifespan and instability due to interfacial barriers and chemical instability of organic interface materials, while inorganic materials lack flexibility and exhibit uneven coverage, leading to non-radiative recombination.

Method used

Incorporation of an interface layer composed of a metallocene compound substituted with O, S, or P atoms between the perovskite layer and the electron transport layer to enhance stability and charge transport.

Benefits of technology

The interface layer improves the efficiency and stability of perovskite solar cells by reducing defects and minimizing non-radiative recombination, applicable to both conventional and inverted PVSC structures, including large-area cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119138121A_ABST
    Figure CN119138121A_ABST
Patent Text Reader

Abstract

A photovoltaic cell includes a perovskite layer (110), an electron transport layer (106), and an interface layer (108) disposed between the electron transport layer and the perovskite layer. The interface layer includes a metallocene substituted with a substituent having an O, S, N or P group, such as a ferrocene substituted with a thienyl carboxylic acid ester group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a material for an interface layer of a metal halide perovskite solar cell and a photovoltaic cell comprising the interface layer. Background Art

[0002] Metal halide perovskites are cheap and easy to manufacture via a range of different manufacturing processes and techniques. Metal halide perovskites are often used as light absorbing layers in thin film solar cells, providing low-cost, lightweight solar cells. Such metal halide perovskite solar cells (metal halide PVSCs) have become a breakthrough photovoltaic technology, with single-junction PVSCs achieving a power conversion efficiency (PCE) of 25.5%. Photovoltaic cells have now surpassed the efficiency of commercial thin film solar cells (such as cadmium telluride CdTe or copper indium gallium selenide CIGS) and are approaching the efficiency of state-of-the-art crystalline silicon solar cells.

[0003] WO2017160955 discloses a perovskite-based photoactive device, such as a solar cell, comprising an insulating tunnel layer interposed between a perovskite photoactive material and an electron collection layer.

[0004] CN113193124 discloses a triethylamine hydrochloride-modified perovskite solar cell, which comprises a transparent conductive glass, a tin dioxide electron transport layer, a triethylamine hydrochloride layer, a perovskite absorption layer, a hole transport layer and a metal electrode arranged in sequence.

[0005] WO2015092397 discloses photovoltaic and optoelectronic devices comprising passivated metal halide perovskites, which comprise (a) a metal halide perovskite; and (b) a passivator, which is an organic compound; wherein molecules of the passivator are chemically bonded to anions or cations in the metal halide perovskite.

[0006] WO2018137048 discloses a perovskite-based optoelectronic device using an electron transport layer, on which a perovskite layer is formed, and the perovskite layer is passivated using a ligand selected to reduce electron-hole recombination at the interface between the electron transport layer and the perovskite layer.

[0007] CN110993803 discloses forming a passivation layer on the perovskite grain boundaries and the perovskite / hole transport layer interface of a perovskite solar cell.

[0008] CN109360889 discloses a solar cell, which is provided with a transparent conductive substrate, a hole transport layer, a perovskite film, an interface passivation layer, an electron transport layer and a cathode in sequence from bottom to top.

[0009] Organic interface materials (OIMs) are known. These organic materials provide flexibility, uniformity, and versatility as interlayers in PVSCs. However, OIMs generally exhibit poor conductivity and carrier mobility, forming interfacial barriers and hindering charge carrier transport. In addition, they exhibit chemical or photochemical instability, which may affect the long-term stability of photovoltaic devices.

[0010] For PVSCs, inorganic interface materials (IIMs) are also known. Such IIMs are usually inherently thermally and chemically stable and exhibit high carrier conductivity and good stability as interlayers in PVSCs. However, they are structurally rigid (not as flexible as organic materials), which hinders close contact and interaction with the perovskite surface. In addition, some inorganic interface materials (such as 2D transition metal chalcogenides) exhibit uneven coverage on the perovskite surface, which may lead to more non-radiative recombination.

[0011] Short lifespan and instability still affect the commercial prospects of PVSCs. It is desirable to address these shortcomings of PVSCs and provide a stable and efficient photovoltaic cell. Summary of the invention

[0012] In a first aspect, the present invention provides a photovoltaic cell comprising:

[0013] a first electrode;

[0014] a second electrode;

[0015] a perovskite layer and an electron transport layer disposed between the first and second electrodes; and

[0016] An interface layer is provided between the perovskite layer and the electron transport layer. The interface layer is in direct contact with the perovskite layer. The interface layer comprises or is composed of an interface compound, wherein the interface compound comprises at least one substituent R 1 Substituted metallocene, the substituent comprises at least one of O, S, N or P atoms.

[0017] Optionally, the interfacial compound is a compound of formula (I):

[0018] [Metallocene]p

[0019] (I)

[0020] in:

[0021] A metallocene is a metallocene group comprising a metallocene radical bonded to two aromatic or heteroaromatic groups Ar 1 of metal;

[0022] p is at least 1; and

[0023] At least one metallocene is substituted with at least one substituent R 1 replace.

[0024] Optionally, the compound of formula (I) has formula (Ia):

[0025]

[0026] in:

[0027] M is a metal ion;

[0028] Ar 1 is a monocyclic or polycyclic aromatic or heteroaromatic group at each occurrence;

[0029] M and two Ar 1 The group forms a metallocene;

[0030] At least one Ar 1 By at least one R 1 replace;

[0031] R 2 is a group that satisfies the valence of M;

[0032] q is 0 or a positive integer; and

[0033] R 3 is independently at each occurrence H or a substituent.

[0034] Optionally, the metallocene is ferrocene.

[0035] Optionally, R 1 is a group of formula (II):

[0036] -AB

[0037] (II)

[0038] wherein A is a divalent group containing O, S, N or P; and B is H, C 1-12 alkyl, optionally substituted aryl, or optionally substituted heteroaryl.

[0039] Optionally, A is selected from the group consisting of:

[0040] -(R 5 ) f -Z-(R 5 )g- (III)

[0041] -(R 6 O) j - (IV)

[0042] in:

[0043] R 5is independently at each occurrence a hydrocarbyl group;

[0044] f and g are each independently 0 or 1;

[0045] R 6 It is C 1-4 Alkylene, preferably ethylene; and

[0046] Z is O, S, COO, C(=S)O, C(=O)S, CONR 4 , CSNR 4 、OC(=O)O、OC(=O)NR 4 、OC(=O)PR 4 ,

[0047] NR 4 , PR 4 ,-OP(=O)(OR 4 )-O-、-NR 4 -P(=O)(NR 4 2)-NR 4 -, where R 4 is H, optionally substituted C 1-12 alkyl or optionally substituted phenyl.

[0048] In some preferred embodiments, the metallocene and R 1 The bond between them is a carbon-oxygen bond, where the C atom of the metallocene is bonded to R 1 of O atoms.

[0049] Optionally, A is -OC(=O)-.

[0050] Optionally, B is selected from optionally substituted phenyl and optionally substituted 5-membered heteroaryl comprising one or more ring atoms selected from O, S and N.

[0051] Optionally, B is optionally substituted thiophene.

[0052] Optionally, the perovskite layer comprises a perovskite of formula CatPbX3 or CatSnX3, wherein Cat is a metal cation, an organic cation or a combination thereof, and X is selected from at least one of I, Br and Cl.

[0053] Optionally, the electron transport layer comprises fullerenes.

[0054] In a second aspect, the invention provides a photovoltaic module comprising a plurality of photovoltaic cells according to any one of the preceding claims, the photovoltaic cells being connected in series.

[0055] In a third aspect, the present invention provides a compound of formula (I):

[0056] [Metallocene]p

[0057] (I)

[0058] in:

[0059] A metallocene is a metallocene group comprising a metallocene radical bonded to two aromatic or heteroaromatic groups Ar 1 of metal;

[0060] p is at least 1; and

[0061] At least one metallocene is substituted with at least one substituent R 1 Substitution, where R 1 is a group of formula (II):

[0062] -AB

[0063] (II)

[0064] wherein A is a divalent group comprising O, S, N or P; and B is optionally substituted aryl or optionally substituted heteroaryl.

[0065] Optionally, according to the third aspect, Ar 1 is optionally substituted cyclopentadienyl.

[0066] Optionally, according to the third aspect, the metallocene is ferrocene.

[0067] Optionally, according to the third aspect, A is selected from a group of the formula:

[0068] -(R 5 ) f -Z-(R 5 )g- (III)

[0069] -(R 6 O) j - (IV)

[0070] in:

[0071] R 5 is independently at each occurrence a hydrocarbyl group;

[0072] f and g are each independently 0 or 1;

[0073] R 6 It is C 1-4 Alkylene, preferably ethylene;

[0074] j is 1-10; and

[0075] Z is O, S, COO, C(=S)O, C(=O)S, CONR 4 , CSNR4 、OC(=O)O、OC(=O)NR 4 、OC(=O)PR 4 ,

[0076] NR 4 , PR 4 ,-OP(=O)(OR 4 )-O-、-NR 4 -P(=O)(NR 4 2)-NR 4 -, where R 4 is H, optionally substituted C 1-12 alkyl or optionally substituted phenyl.

[0077] Optionally, according to the third aspect, A is -OC(=O)-.

[0078] Optionally, according to the third aspect, B is selected from optionally substituted phenyl and optionally substituted 5-membered heteroaryl comprising one or more ring atoms selected from O, S and N.

[0079] Optionally, according to the third aspect, B is optionally substituted thiophene. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1A A schematic diagram of a conventional perovskite solar cell including an interfacial layer is provided, and Figure 1B A schematic diagram of an inverted perovskite solar cell including an interface layer is provided;

[0081] Figure 2 Substituted metallocenes suitable for use in interfacial layers are shown;

[0082] Figure 3: Figure 3A Provided are materials having FcTc2 interface functionalization Figure 1B Schematic diagram of an exemplary inverted perovskite solar cell, Figure 3B Shows the manufacturing of Figure 3A The cross-sectional SEM image of the inverted PVSC structure and Figure 3C Shows Figure 3B TOF-SIMS characterization of perovskite solar cells;

[0083] Figure 4: Figure 4A X-ray photoelectron spectroscopy (XPS) characterization of the binding energy of Pb is shown, Figure 4B The XPS characterization of N is shown, and Figure 4C The XPS characterization of I is shown;

[0084] FIG5 shows surface potential images obtained by scanning Kelvin probe microscopy of perovskite films, where the lower image is a control device ( Figure 5A ) and FcTc2-treated perovskite films including an interfacial layer ( Figure 5B )’s statistical potential distribution on the membrane surface;

[0085] Figure 6 Time-resolved photoluminescence (TRPL) spectra of a device comprising perovskite / FcTc2 / C60 (with an interfacial layer) and a device comprising perovskite / C60 (control) are shown;

[0086] Figure 7 The results show that the FcTc2 with different concentrations (0, 0.5, 1.0 and 2.0 mg mL -1 )’s steady-state PL spectra of the perovskite film;

[0087] Figure 8 shows that at 1480 cm -1 PFIR microscopy at IR frequencies (which resonate with the CN stretch absorption of MA+ ions): Fig. 8A shows the FcTc2-modified perovskite film before irradiation, Figure 8B shows the FcTc2-modified perovskite film after irradiation at 85 °C for 1000 h, Figure 8C A control perovskite film before irradiation is shown, and Fig.8D A control perovskite film after irradiation at 85 °C for 1000 h is shown;

[0088] Fig. 9 JV curves of the best performing devices with and without the FcTc2 interfacial layer are shown;

[0089] Fig.10 EQE spectra and integrated current density of the best performing devices with and without FcTc2 are shown;

[0090] Fig.11 shows a histogram of PCE values ​​measured in 30 devices with and without FcTc2;

[0091] Fig.12 The normalized PCE values ​​of unencapsulated PVSCs with and without FcTc2 measured at the maximum power point (MPP) under continuous one-sun irradiation in N2 atmosphere and room temperature are shown;

[0092] Figure 13 shows the continuous heating at 85°C in N2 atmosphere ( Fig.13A ) and stored in dark ambient air (RH 40-50%, 25°C) ( Fig. 13B ), based on the stability test results of unencapsulated devices with and without FcTc2;

[0093] FIG. 14 shows a packaged device stored in the dark at 85% RH and 85°C ( Fig.14A ) and packaged devices stored at -40°C (15 min dwell), heated to 85°C (15 min dwell), at a heating rate of 100°C / h ( Fig. 14B )’s normalized PCE data;

[0094] Fig.15 A shows the JV curves of the best performing MAPbI3-based PVSCs with and without FcTc2, and Fig.15 B shows a histogram of the PCE values ​​measured in 20 devices of MAPbI3-based PVSCs with and without FcTc2;

[0095] Fig.16 A shows the best performance of Cs with and without FcTc2 0.05 (FA 0.85 MA 0.15 ) 0.95 Pb(I 0.85 Br 0.15 ) JV curve of 3-based PVSC, and Fig.16 B shows the Cs with and without FcTc2 0.05 (FA 0.85 MA 0.15 ) 0.95 Pb(I 0.85 Br 0.15 ) Histogram of the PCE values ​​measured in 20 devices of 3-based PVSC;

[0096] Fig.17 A shows the JV curves of the best performing FAPbI3-based PVSCs with and without FcTc2, and Fig.17 B shows a histogram of the PCE values ​​measured in 20 devices of FAPbI3-based PVSCs with and without FcTc2;

[0097] Fig.18 A and 18B show a purely electronic device structure with ( Fig.18 A) and does not have ( Fig.18 B) SCLC curves of the perovskite film of FcTc2, and Fig.18 C shows the TRPL spectra of perovskite / FcTc2 / C60 and perovskite / C60;

[0098] Fig.19 The control device ( Fig.19 A) and a device with an FcPh2 interface layer ( Fig.19 B) JV curve of the best performance device of PVSC;

[0099] Fig. 20 The control device ( Fig. 20 A) and a device with a DPC interface layer ( Fig. 20 B) JV curve of the best performance device of PVSC;

[0100] Fig.21 The control device ( Fig. 20 A) and devices with BA interfacial layer ( Fig. 20 B) JV curve of the best performance device of PVSC;

[0101] FIG. 22 shows the solution ( Fig.22A ) and thin films ( Fig. 22B ) UV-vis spectrum of FcTc2;

[0102] Fig.23 Density functional theory (DFT) simulations of the interaction between FAPbI3 and FcTc2 molecules are shown; and

[0103] Fig.24 Electrostatic potential (ESP) analysis of FcTc2 is shown.

[0104] Fig.25 Surface molecular interactions are shown: a, functionalized Fc-based compound structure. b, electrostatic potential of Fc-based compounds via DFT simulation. c, d, XPS spectra of elemental Pb and I; e, XPS spectra of Fe within different Fc compounds on the perovskite surface. f, g, EFM characterization of phase images of perovskite films with and without Fc compounds, where a bias (-3 to 3 V, 1.5 V step) was supplied to the tip to enable extraction of Coulomb forces. h, Phase diagram with respect to the applied bias.

[0105] Fig.26 Potential evolution and carrier dynamics are shown: ad, KPFM of surface contact potential difference (CPD) of perovskite films treated with different Fc compounds, eh, statistics of surface work function of perovskite films, i, TRPL spectra of perovskite / ETL films with different Fc compounds. j, integrated fitting value of PL spectrum intensity of perovskite / ETL films with different Fc compounds, k, trap filling voltage V of perovskite devices with different Fc compounds TFL And statistics of EL value EQE.

[0106] Fig. 27PV performance is shown: a, Schematic diagram of the device structure. b, Cross-sectional SEM image of the PSC. c, JV curves of the best performing PSC treated with different Fc compounds. d, Highest PCE of PSC treated with different Fc compounds. e, JV curves of the forward and reverse scans of the device with Fc2Tc2. f, EQE and integrated current density. g, Stable power output of the Fc2Tc2 treated PSC. h, PV parameter statistics of the control and Fc2Tc2 treated PSC. The mask area is 0.0414 cm 2 .

[0107] Fig.28 The PV performance and uniformity of large-area devices are shown: a, mask area is 1.008 cm 2 JV curves of the original and Fc2Tc2 treated PSCs with the best performance. b, Stable power output of large-area PSCs treated with Fc2Tc2. Inset is the top-view device image. c, V OC Statistical distribution of FF and d, the aperture area selected from the total effective area is 0.0414 cm 2 JV curves of a representative Fc2Tc2 treated PSC measured at five different points on the device. e, Statistics of normalized PV parameters and CV values ​​for a small area selected from a large area PSC. Data were recorded from five independent points on four devices and normalized relative to the highest value of the highest value for each parameter. f, Statistics of normalized PL on perovskite / ETL with and without Fc2Tc2 treatment. CV is the coefficient of variation. Fig.29 AE show the JV curves of functionalized ferrocene compounds for perovskite solar cells.

[0108] Fig.30 The efficiency evolution of large-area and small-area PSCs with conventional and inverted structures, as well as the efficiency gap between large-area and small-area PSCs are shown. Fig.31 Shown are the XPS spectra of elemental Pb in perovskite films with different Fc compounds.

[0109] Fig.32 XPS spectra of element I in perovskite films with different Fc compounds are shown.

[0110] Fig.33 Shown are the UV-vis absorption spectra of perovskite films with different Fc compounds.

[0111] Fig.34 AFM images of perovskite films with different Fc compounds are shown.

[0112] Fig.35Shown are: a, c, EFM features of phase images of perovskite films with FcTc2 and Fc3Tc2 compounds, where a bias (-3 to 3 V, 1.5 V steps) was supplied to the tip to enable extraction of Coulomb forces. b, d, Phase images of perovskite films with FcTc2 and Fc3Tc2 compounds with respect to the applied bias.

[0113] Fig.36 Statistics of the phase angle of the pristine perovskite film at different applied bias voltages are shown.

[0114] Fig.37 Statistics of the phase angles of Fc-modified perovskite films at different applied biases are shown.

[0115] Fig.38 TOF-SIMS images of Fc2Tc2-modified perovskite solar cells are shown. Fig.39 Steady-state PL spectra of perovskite films treated with different Fc compounds are shown.

[0116] Fig.40 Shown are PL spectra of perovskite films modified with a) control, b) FcTc2, c) Fc2Tc2, and d) Fc3Tc2.

[0117] Fig.41 Dektak XTL-based perovskite film thickness measurements are shown.

[0118] Fig.42 SCLC characterization of the defect density of pristine and modified perovskite films with different Fc-based compounds based on pure electronic devices (FTO / TiO2 / perovskite / Fc / C60 / BCP / Ag) is shown.

[0119] Fig.43 The light-independent open-circuit voltages of pristine PSCs and Fc-modified PSCs are shown.

[0120] Fig.44 Shown are EL spectra of perovskite devices with a) control, b) FcTc2, c) Fc2Tc2, and d) Fc3Tc2 at different bias voltages operated as LEDs.

[0121] Fig.45 The EQE of the EL graphs of control, FcTc2, Fc2Tc2, and Fc3Tc2 treated PSCs are shown.

[0122] Fig.46 JV curves of the forward and reverse scans of the best performing pristine PSC are shown.

[0123] Fig.47JV curves of the best performing PSCs modified with different concentrations of Fc2Tc2 are shown.

[0124] Fig.48 Shown are the PCE statistics of PSCs modified with different Fc compounds and at different concentrations.

[0125] Fig.49 The sensitive EQE of original and Fc2Tc2-treated PSCs are shown.

[0126] Fig.50 Statistics of energy loss of control and Fc2Tc2-treated PSCs are shown.

[0127] Fig.51 Long-term operational stability measurements of packaged devices at room temperature, in N2 atmosphere, and under AM 1.5G simulated sunlight irradiation are shown. One point is selected from every 70 points as a representative point shown in each curve.

[0128] Fig.52 Shown are the 5-point PL spectra of a) pristine perovskite / ETL film and b) Fc2Tc2-treated perovskite / ETL film.

[0129] Fig.53 KPFM images and potential distributions of the control film at three different locations are shown.

[0130] Fig.54 KPFM images and potential distribution of Fc2Tc2-treated films at three different locations are shown. DETAILED DESCRIPTION

[0131] refer to Figure 1A , describes a "conventional" perovskite photovoltaic cell (also referred to herein as a perovskite solar cell) 100a comprising an np or nip junction (where electrons are collected at a transparent electrode). Figure 1B , describes an "inverted" perovskite photovoltaic cell (also referred to herein as a perovskite solar cell) 100b comprising a pn or pin junction (where holes are collected at a transparent electrode). Figure 1A and Figure 1B ) in the discussion of the present invention, similar figure numbers represent similar features.

[0132] Among perovskite solar cells (PVSCs), inverted (pn / pin structure) devices generally exhibit more stable behavior than conventional (np / nip) PVSCs, in part due to their non-doped hole transport materials and highly crystalline perovskite films. The following description mainly refers to inverted PVSCs, but the beneficial effects of the interfacial layers described herein are equally applicable to conventional (nip) PVSC structures.

[0133] A transparent substrate 102 is provided. This forms the base or support of the solar cell structure 100. The photovoltaic cell (solar cell 100) can be implemented as a tandem solar cell. For example, the solar cell 100 can be implemented as a tandem perovskite / silicon solar cell. In this arrangement, the perovskite layer, the electron transport layer, and the interface layer can be provided as part of a perovskite cell, which is formed on a silicon cell or built on top of a silicon cell to form a tandem photovoltaic cell (solar cell 100). Visible light 116 (such as incident sunlight) enters the solar cell 100 (e.g., solar cell 100a or 100b) through the transparent substrate 102. The substrate 102 can be formed of glass or any other suitable transparent material.

[0134] The solar cell 100 (e.g., solar cell 100a or 100b) includes a perovskite layer 110. In use, the perovskite layer 110 absorbs light incident on the solar cell 100. The term "light absorption" in relation to the perovskite (and by extension to the layer 110 comprising the one or more perovskites) refers to its role in absorbing light (e.g., visible light 116), thereby acting as a light absorbing material, allowing the light 116 to be converted into electrical energy. The perovskite compound exhibits strong absorption of the visible light 116 incident on the solar cell 100, and the band gap of the perovskite semiconductor can be adjusted to a desired band gap energy E g , thereby improving the efficiency of such solar cells.

[0135] In the exemplary solar cell depicted in FIG1 , solar radiation or visible light 116 enters the active layer 110 through the substrate layer 102, whereupon at least a portion of the solar radiation 116 is absorbed by exciting electrons to cross the semiconductor band gap, thereby enabling power generation. Specifically, electrons are excited from the valence band of the semiconductor, cross the band gap, and reach the conduction band. The excited electrons are located in the conduction band, and the corresponding holes (vacancies or absences of electrons, not the physical particles themselves) remain in the valence band of the semiconductor.

[0136] The asymmetry within the functional layer 110 is used to separate excited electrons from holes, thereby moving charge carriers (holes and electrons) away from electron promotion sites for collection and current generation. In the examples described herein, this asymmetry is provided by junctions within the perovskite layer 110 (such as Figure 1A The np or nip junction of the solar cell 100a, or Figure 1B 100b in the pn or pin junction of the solar cell 100b). Therefore, it will be understood that the perovskite layer may include any suitable semiconductor junction. However, the asymmetry within the perovskite layer may be provided in any other suitable manner.

[0137] In some examples, the perovskite layer 110 may include one or more heterojunctions. A heterojunction may be formed in the perovskite layer 110 by two different, undoped perovskite materials. Therefore, the perovskites mentioned herein may all be undoped semiconductors. Alternatively, the perovskites may be doped with p-type or n-type dopants to form a junction. In other words, they may be doped (over the entire surface and / or at the surface) with at least one dopant material having a higher valence than the bulk material (to provide n-type doping) and / or may be doped with at least one dopant material having a lower valence than the bulk material (to provide p-type doping). N-type doping tends to increase the n-type characteristics of the semiconductor material, while p-type doping tends to reduce the degree of the natural n-type state (e.g., due to defects). Such doping may be performed with any suitable material, including F, Sb, N, Ge, Si, C, In, InO, and / or Al. Suitable dopants and doping levels are apparent to those skilled in the art.

[0138] In some examples, the light absorbing perovskite layer 110 includes one or more metal halide perovskites. In some examples, the light absorbing layer can include two different metal halide perovskites configured to form a semiconductor heterojunction within the layer 110. Any perovskite capable of performing the desired light absorption and charge separation functions can be used in the light absorbing layer 110.

[0139] With further reference to the solar cell 100, an electron transport layer ETL 106 is provided. The ETL (or n-type charge extraction layer) comprises an electron transport material. Any electron transport material known to the skilled person may be used. The ETL may comprise an organic electron transport material, an inorganic electron transport material, or a mixture thereof, or may consist of an organic electron transport material, an inorganic electron transport material, or a mixture thereof. Examples of electron transport materials include organic materials such as fullerenes, metal oxides such as TiO2, ZnO, SnO2, SiO2, or ZrO2.

[0140] Fullerenes are preferred. Fullerenes can be selected from any known fullerenes, including C 60 Fullerene and C 70 Fullerenes, each of which is optionally substituted with one or more substituents. Exemplary substituents include C 1-12 Alkyl, where C 1-12 One or more non-adjacent C atoms of the alkyl group may be substituted with O, S, CO or COO and an optionally substituted phenyl group, and two substituents may be linked to form a monocyclic or polycyclic ring. Exemplary fullerenes include C 60 , PCBM and ICBA.

[0141] The electron transport material can facilitate the flow of electrons from the n-type perovskite, leaving the junction within the layer 110, while preventing the movement of holes. In this way, electrons accumulate at the first electrical conductor 104. In use, due to the accumulation of electrons, the first electrical conductor 104 is negatively charged. When the solar cell is connected to an external load, the electrons leave the solar cell 100 via the first electrical conductor 104.

[0142] A hole transport layer HTL 112 comprising or consisting of one or more hole transport materials may also be provided within the solar cell 100. Figure 1B In an inverted PVSC, the HTL is located near the transparent substrate (holes are collected at the electrodes near the substrate, Figure 1A Any hole transport material known to the skilled person may be used.

[0143] Exemplary hole transport materials include organic hole transport materials, inorganic hole transport materials, or combinations thereof. Organic hole transport materials can be polymeric or non-polymeric. Exemplary polymeric hole transport materials include polythiophenes, such as poly(3-hexylthiophene) (P3HT); poly(arylamines), such as PTTA; and doped PEDOT, such as PEDOT:PSS. Exemplary non-polymeric organic hole transport materials are compounds containing one or more arylamine groups, such as spiroOMeTAD. Exemplary inorganic hole transport materials include copper-based materials (e.g., CuC x , CuSCN, CuI, etc.), nickel-based materials (e.g., NiO x ), two-dimensional layered materials such as chalcogens (e.g., MoS2, WS2, etc.). The hole transport material promotes the flow of holes from the p-type perovskite, leaving the junction within the layer 110, while preventing the movement of electrons. In this way, holes accumulate at the second electrical conductor 114. In use, due to the accumulation of holes, the second electrical conductor 114 is positively charged.

[0144] In a conventional PVSC, the first conductor 104 can be any transparent conductive material. In some examples, the first conductor 104 is a transparent conductive film (TCF). In some examples, the TCF is a transparent conductive oxide (TCO) layer. In some examples, the TCO layer contains indium tin oxide (ITO), fluorine-doped tin oxide (FTO) or doped zinc oxide. The second conductor 114 can be formed of any suitable conductive material, such as Ag, Au, Cu, etc. In an inverted PVSC, the second conductor 114 can be any transparent conductive material (because in the inverted structure, it is this contact that is set on the transparent substrate 102), such as a transparent conductive film, or more specifically a TCO. Then, the first conductor 104 can be formed of any suitable conductive material, such as Ag, Au, Cu, Al, etc. The first and second conductors or contacts are used to connect to an external load.

[0145] In previous PVSCs, the functional or active perovskite layer 110 is sandwiched between the HTL 112 and the ETL 106. In other words, the charge transport layers are deposited on the top and bottom sides of the perovskite active layer, respectively. Charge carriers are extracted at the HTL / perovskite and perovskite / ETL interfaces and collected by the corresponding conductors / contacts. During this process, carrier charges may recombine, for example due to any interface defects and the associated specific charge distribution.

[0146] Interfacial recombination arises from the charge dynamics at the interface (including charge extraction, charge transfer, and charge recombination). Imperfect interface structure and electron mismatch usually become energy barriers for charge transfer and charge recombination. In addition, most of the defects on the surface and interface of polycrystalline perovskite films are positively or negatively charged. Trap states on the perovskite surface and interface can lead to charge accumulation and recombination losses in the device.

[0147] It has been found that the performance of the perovskite solar cell described herein can be improved when an interfacial layer 108 comprising an interfacial compound as described herein is provided between the electron transport layer 106 and the perovskite layer 110. Such a layer can suppress defects in the perovskite surface and minimize interface non-radiative combination losses. In this way, the interfacial layer 108 improves electron extraction at the perovskite interface, thereby improving the efficiency of the solar cell; and improves the stability of the solar cell 100.

[0148] The interface layer 108 directly interfaces with the perovskite layer 110. In other words, the interface layer 108 and the perovskite layer are in direct contact. As described below, the interface layer 108 can be deposited directly on the active perovskite layer 110, or can be formed in other ways. The interface layer 108 is described in more detail below.

[0149] One or more additional layers (not shown) may be provided within the solar cell structure 100. For example, one or more optional hole blocking layers may be provided between the ETL 106 and the contact 104 and / or between the interface layer 108 and the ETL 106. Similarly, one or more optional electron blocking layers may be provided between the HTL 112 and the contact 114 and / or between the perovskite layer 110 and the HTL 112. Any other layers may be provided within the solar cell 100 as appropriate.

[0150] Multiple photovoltaic cells 100a, 100b can be connected in series and packaged to form a photovoltaic module (not shown). Depending on the power required for a specific load or application, a photovoltaic module can be used alone, or multiple photovoltaic modules can be connected in series and / or in parallel to form a photovoltaic array.

[0151] Interface layer

[0152] The interfacial layer comprises or consists of a metallocene substituted with at least one substituent containing an O, S, N or P atom having a lone pair of electrons.

[0153] The inventors surprisingly found that the presence of such an interfacial layer can enhance the stability and performance of perovskite solar cells. In addition, the inventors found that these benefits can be achieved on large area cells (e.g., up to 30 cm x 30 cm, such as up to 15 cm x 15 cm). Optionally, the cell area is at least 1 x 1 cm.

[0154] Without wishing to be bound by any theory, it is believed that the flexibility of the metallocene around the metal-aromatic bonding can improve the stress between the electron transport layer and the perovskite layer.

[0155] Again, without wishing to be bound by any theory, it is believed that the lone electron pairs of the O, S, N or P groups can bind to uncoordinated metal defects at the perovskite surface, such as Pb defects.

[0156] The metallocene is preferably a compound of formula (I):

[0157] [Metallocene]p

[0158] (I)

[0159] in:

[0160] A metallocene is a metallocene group comprising a metallocene radical bonded to two aromatic or heteroaromatic groups Ar 1 of metal;

[0161] p is at least 1, optionally 1, 2 or 3; and

[0162] At least one metallocene is substituted with at least one substituent R 1 Substitution, where R 1 is a group containing O, S, N or P atoms.

[0163] Optionally, the compound of formula (I) has formula (Ia):

[0164]

[0165] in:

[0166] M is a metal ion;

[0167] Ar 1 is a monocyclic or polycyclic aromatic or heteroaromatic group at each occurrence;

[0168] M and two Ar 1 The group forms a metallocene;

[0169] At least one Ar1 By at least one R 1 Substitution, where R 1 is a group containing O, S, N or P atoms;

[0170] R 2 is a group that satisfies the valence of M;

[0171] q is 0 or a positive integer, preferably 0 or 2;

[0172] R 3 is independently at each occurrence H or a substituent; and

[0173] p is at least 1.

[0174] Exemplary Ar 1 The group includes, but is not limited to, C4-C8 aromatic groups, i.e., cyclobutadiene, cyclopentadienyl, benzene, cycloheptatrienyl or cyclooctatetraene; and C5 heteroaromatic groups, such as pyrrole, each of which may be unfused or fused to one or more additional rings, preferably one or more benzene rings. Exemplary fused groups Ar 1 Includes benzocyclopentadienyl and fluorenyl.

[0175] The metallocene preferably comprises two cyclopentadienyl groups Ar 1 Metal M. Ar 1 The radical may consist of a cyclopentadienyl radical or the cyclopentadienyl radical may be fused to one or more further rings, preferably one or more aromatic rings, for example one or more benzene rings as in benzocyclopentadienyl or fluorenyl.

[0176] M can be Fe 2+ 、Co 2+ Cr 2+ 、Ni 2+ or V 2+ , preferably Fe 2+ For each of these compounds, q is 0.

[0177] M can be Zr or Ti. For each of these compounds, q is 2, and R 2 It may be any suitable group capable of bonding to Zr or Ti, for example methyl, amine, dialkylamine, phosphine, CO or a halogen, for example Cl such as in a metallocene dihalide.

[0178] The metallocene or the two Ar 1 The group may be linked via a divalent group other than M, such as C 1-6 Alkylene or formula Si(R 3 )2, wherein R 3 C independently at each occurrence 1-12Hydrocarbon, such as C 1-12 Thus, it will be understood that compounds of formula (I) include ansa-metallocenes.

[0179] In a preferred embodiment, M and Ar 1 Forming ferrocene, that is, M is Fe; each Ar 1 is cyclopentadienyl; and y is 0.

[0180] Preferably, R 1 It is Ar 1 The only substituent of a group.

[0181] Preferably, p is 1, 2 or 3, more preferably 1.

[0182] The compound of formula (Ia) may be selected from formula (Ib), (Ic) or (Id):

[0183]

[0184] wherein t1 is 0, 1 or 2, preferably 0 or 1; t2 is 0 or 1, preferably 1; and at least one of t1 and / or t2 is at least 1.

[0185] In some embodiments, R 1 is a group of formula (II):

[0186] -AB

[0187] (II)

[0188] wherein A is a divalent group containing O, S, N or P; and B is H, C 1-12 alkyl, optionally substituted aryl, or optionally substituted heteroaryl.

[0189] The group A may include any group capable of binding to Pb. Exemplary groups A include, but are not limited to, ethers, thioethers, amines, phosphines, phosphoryl ethers, carbonates, carbamates, carboxylates, amides, thioamides, phosphonamides, thiocarboxylates, aminocarboxylates, and phosphocarboxylates. R1 may contain only one group A. R 1 Two or more groups A may be contained.

[0190] Exemplary groups A include groups of formula (III) and (IV):

[0191] -(R 5 ) f -Z-(R 5 )g- (III)

[0192] -(R 6 O) j - (IV)

[0193] in:

[0194] R 5 is independently at each occurrence a hydrocarbyl group;

[0195] f and g are each independently 0 or 1;

[0196] R 6 It is C 1-4 Alkylene, preferably ethylene;

[0197] j is 1-10; and

[0198] Z is O, S, COO, C(=S)O, C(=O)S, CONR 4 , CSNR 4 、OC(=O)O、OC(=O)NR 4 、OC(=O)PR 4 ,

[0199] NR 4 , PR 4 ,-OP(=O)(OR 4 )-O- or -NR 4 -P(=O)(NR42)-NR 4 -, where R 4 is H, optionally substituted C 1-12 alkyl or optionally substituted phenyl.

[0200] Hydrocarbon R 5 Preferably selected from C 1-6 alkylene; optionally substituted phenylene; and C 1-6 Alkylene-phenylene.

[0201] R 5 The phenylene group may be unsubstituted or substituted with one or more selected from C 1-6 The alkyl group is substituted with a substituent.

[0202] In R 5 It is C 1-6 In the case of alkylene-phenylene, the group Z can be bonded to the alkylene or the phenylene.

[0203] A particularly preferred group A is -OC(=O)-, which can be bonded to the metallocene via an O atom or a C atom, preferably via an O atom.

[0204] B is preferably an optionally substituted aryl or heteroaryl, more preferably phenyl or a 5-membered heteroaromatic compound comprising one or more of N, S and O ring atoms, such as furan, thiophene, pyrrole, imidazole and oxazole. Thiophene is particularly preferred.

[0205] Optional substituents for optionally substituted alkyl or alkylene groups described anywhere herein include F, Cl, OR 4 and NR42, where R 4 It is C 1-6 alkyl.

[0206] The optional substituents of any optionally substituted aromatic or heteroaromatic group described anywhere herein, including but not limited to the substituents R of formula (Ia) 3 , including F, Cl, CN, NO2, C 1-6 Alkyl, in which one or more H atoms may be replaced by F, OR 4 and NR42, where R 4 It is C 1-6 alkyl.

[0207] Without wishing to be bound by any theory, the electron-rich heteroaryl group B may form a coordination bond with the Pb of the perovskite. The coordination bond may be in addition to or in place of the bond of the group A. Thus, in some embodiments, R 1 It may be a 5-membered heteroaromatic group of formula B as described above.

[0208] refer to Figure 2 , showing the structure of an exemplary compound of the interface layer 108. In one specific example, the interface layer 108 includes ferrocenyl-bis-thiophene-2-carboxylate (FcTc2) as an interface functionalization material to enhance the efficiency and stability of the PVSC. Fig.22A and 22B The ultraviolet-visible (UV-vis) absorption spectra of FcTc2 in solution and film form are provided in FIG.

[0209] Perovskite

[0210] The perovskite may be any material having a CatBX3 crystal structure (perovskite structure, often referred to as an "ABX3" structure), wherein Cat and B are cations, and X is an anion. B is preferably Pb or Sn.

[0211] The perovskite is suitably a perovskite of the formula CatPbX3 or CatSnX3, wherein Cat is a metal cation, an organic cation or a combination thereof, and X is selected from at least one of I, Br and Cl.

[0212] Exemplary groups Cat include alkali metal cations, preferably Cs; ammonium cations, such as methylammonium; and amidinium ions, such as formamidinium.

[0213] Preferably, X comprises two of I, Br and Cl.

[0214] Preferably, Cat comprises a metal cation and an organic cation.

[0215] Preferably, Cat contains two different organic cations.

[0216] Examples of perovskites suitable for use as the light-absorbing layer include: ammonium trihalide lead, such as CH3NH3PbI3, CH3NH3PbCl3, CH3NH3PbF3, and CH3NH3PbBr3; mixed halide ammonium trihalide lead perovskites having the general formula CH3NH3Pb[Hal1] 3-x [Hal2] x where [Hal1] and [Hal2] are independently selected from F, Cl, Br, and I, provided that [Hal1] and [Hal2] are not the same, and where 0 < x < 3, preferably where x is an integer (e.g., 1, 2, or 3, preferably 1 or 2); CsSnX3 perovskites, where X is selected from F, Cl, Br, and I, preferably I; organometallic trihalide perovskites of the general formula (RNH3)BX3, where R is CH3, C n H 2n or C n H 2n+1 n is an integer in the range 2 ≤ n ≤ 10, preferably 2 ≤ n ≤ 5, e.g., n = 2, n = 3, or n = 4, most preferably n = 2 or n = 3, X is a halogen (F, I, Br, or Cl), preferably I, Br, or Cl, and B is Pb or Sn; and combinations thereof. In some examples, a perovskite composition of Csx(FA y MA1-y) 1-x Pb(I z Br 1-z )3 is used, where x = (0 to 0.95), y = (0 to 1), z = (0 to 1), where MA and FA represent methylammonium and formamidinium, respectively.

[0217] Photovoltaic cell formation

[0218] The photovoltaic cells described herein can be formed by any method known to those skilled in the art. Preferably, the perovskite layer and the interface layer are each formed by depositing a solution containing the perovskite and a solution containing the metallocene. Suitable solvents for depositing the perovskite layer include polar solvents such as DMF and DMSO. Preferably, the solvent for depositing the metallocene is selected from chlorinated alkanes, such as chloroform; and unsubstituted or substituted benzene with one or more substituents selected from C 1-6 alkyl, C 1-6 alkoxy, and chlorine, such as dichlorobenzene.

[0219] The solution can be deposited by any method known to those skilled in the art, such as spin coating, dip coating, slot-die coating, blade coating, and bar coating.

[0220] Examples

[0221] As described herein, the chemicals used include the following:

[0222] • Perovskite precursors, cesium iodide (CsI), methylammonium iodide (FAI), methylammonium chloride (MACl), and methylammonium bromide (MABr), were purchased from Dysol (Australia).

[0223] Lead iodide (PbI2) and lead bromide (PbBr2) were purchased from TCI (Japan).

[0224] C60, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) (Mn 6,000-15,000), methylammonium chloride (MACl) and bathocuproine (BCP, purity 99.9%) were purchased from Xi'an Polymer Light Technology Corporation (China).

[0225] • Copper(I)thiophene-2-carboxylate (CuTC) was purchased from Sigma-Aldrich.

[0226] Solvents, including dimethylformamide (DMF), dimethyl sulfoxide (DMSO), isopropyl alcohol (IPA), and chlorobenzene (CB), were purchased from J&K (China) and used as received.

[0227] Acetonitrile (MeCN), dichloromethane (DCM), and hexane were purchased from Sigma-Aldrich and used as received.

[0228] High purity silver was purchased from commercial sources.

[0229] ·Glass substrate patterned with ITO (15Ωsq -1 ) was obtained from Mishi Tech. Co., Ltd. (China).

[0230] FcTc2——Synthesis 1

[0231] A solution of FcI2 (1.0-2.50 mmol), copper thiophene carboxylate (3.2-9.5 mmol) and 9,10-dihydroanthracene (1.5-5.5 mmol) in MeCN was stirred at 50-90 ° C for 1-5 days. After cooling to room temperature, DCM was added and the blue-green reaction mixture was filtered on diatomaceous earth. The solvent was then removed, the crude mixture was dissolved in hexane, and passed through a silica gel pad (about 5 cm), and the desired product was eluted in a 50% DCM hexane solution. After removing the solvent, FcTc2 was obtained as a yellow solid.

[0232] FcTc2——Synthesis 2

[0233] By FcI2 (0.70g, 1.60mmol), copper thiophene carboxylate (1.2g, 6.32mmol) and 9,10- dihydroanthracene (0.60g, 3.33mmol) in MeCN (30mL) solution was stirred at 80 ° C for 2 days. After cooling to room temperature, DCM (50mL) was added and the blue-green reaction mixture was filtered on diatomite. The solvent was then removed, the crude mixture was dissolved in hexane, and by silica gel pad (about 5cm), the desired product was eluted in 50% DCM hexane solution. After removing the solvent, FcTc2 was obtained as a yellow solid (0.17g, 0.38mmol, 24%). 1 H NMR (400MHz, CDCl3, 298K): δ (ppm) 7.78 (dd, J=3.7, 1.3Hz, 2H, Thio-H), 7.56 (dd, J=5.0, 1.3Hz, 2H, Thio-H ), 7.06(dt,J=5.0,3.7Hz,2H,Thio-H), 4.68(t,J=2.0Hz,4H,(CpTc)mH), 4.10(t,J=2.0Hz,4H,(CpTc)oH). 13 C{ 1 H}NMR (100MHz, CDCl3, 298K): δ (ppm) 160.3 (2C, C=O), 134.2 (2C, ThioC-H), 133.3 (2C, ThioC-CO2Fc),133.2(2C,ThioC-H),128.0(2C,ThioC-H),116.6(2C,CpC-O),64.8(4C,

[0234] (CpTc)oCH), 62.2 (4C, (CpTc)mCH). MS ES+: m / z 437.9677 ([M]+ calculated: 437.9683).

[0235] Fc2Tc2——Synthesis

[0236] The structure of Fc2Tc2 Fig.25 Not shown.

[0237] Ferrocenyl-bis-thiophene-2-carboxylate (FcTc2) was synthesized via a previously reported route (Z. Li, B. Li, X. Wu. SA Sheppard, S. Zhang, D. Gao, N. J. Long, and Z. Zhu, Science, 2022, 376, 416-420).

[0238] By Fc2I2 (0.50g, 0.80mmol) (previously reported in MS Inkpen, S. Scheerer, M. Linseis, AJP White, RF Winter, T. Albrecht and NJ Long, Nat. Chem., 2016, 8, 825-830) and 9,10- dihydroanthracene (0.43g, 2.41mmol) in MeCN (100mL) solution with nitrogen bubble 1 hour, then add CuTc (1.53g, 8.04mmol). The green-brown reaction mixture was stirred at 80 ° C for 2 days. Then the solvent was removed and the mixture was filtered on diatomaceous earth with DCM. Then the crude mixture was dissolved in hexane, and purified by silica gel plug (hexane → hexane / DCM (1: 1), Fc2Tc2 (60mg, 0.10mmol, 14%) was obtained. 1 H NMR (400MHz, CDC13, 298K): δ (ppm) 7.76 (dd, J=3.8, 1.3Hz, 1H, Thio-H), 7.59 (dd, J=5.0, 1.3Hz, 1H, Thio-H), 7.11 (dd, J=5.0, 3.8Hz, 1H, Thio -H), 4.44(t,J=1.9Hz,4H,(Cp-Cp)mH), 4.39(t,J=2.0Hz,4H,(CpTc)mH), 4.16(t,J=1.9Hz,4H,(Cp-Cp)oH), 3.81(t,J=2.0Hz,4H,(CpTc)oH). 13 C{ 1 H}NMR (100MHz, CDCl3, 298K): δ (ppm) 160.4 (2C, C=O), 134.2 (2C, ThioC-H), 133.5 (2C, ThioC-CO2Fc), 133.0 (2C, ThioC-H), 127.9 (2C, Thio C-H), 116.3 (2C, CpC-O), 84.4 (2C, CpC-CCp), 69.2 (4C, (Cp-Cp)oCH), 67.7 (4C, (Cp-Cp)mCH), 64.5 (4C, (CpTc)oCH), 62.0 (4C, (CpTc)mCH). MS ES+: m / z 621.9653 ([M]+calculated: 621.9658).

[0239] Fc3Tc2 - Synthesis

[0240] The structure of FC3TC2 is Fig.25 Not shown.

[0241] MeCN (100 mL) was added to Fc3I2 (0.60 g, 0.74 mmol) (previously reported in MS Inkpen, S. Scheerer, M. Linseis, AJP White, RF Winter, T. Albrecht and NJ Long, Nat. Chem., 2016, 8, 825-830), CuTc (0.30 g, 1.58 mmol) and 9,10 dihydroanthracene (0.20 g, 1.11 mmol). The blue-green reaction mixture was stirred at 80 ° C for 2 days. The solvent was then removed and the mixture was filtered on diatomaceous earth with DCM. The crude mixture was then purified by alumina (V) column chromatography, with Fc3Tc2 (20 mg, 0.03 mmol) eluted in 40% DCM hexane solution. 1 H NMR (400 MHz, CDC13, 298 K): δ (ppm) 7.73 (dd, J = 3.7, 1.3 Hz, 2H, Thio-H), 7.58 (dd, J = 5.0, 1.3 Hz, 2H, Thio-H), 7.11 (dt, J = 5.0, 3.7 Hz, 2H, Thio-H), 4.34 (pseudo-t, J = 2.0 Hz, 4H, (CpTc)mH), 4.29 (pseudo-t, 4H, J = 1.8 Hz, (Cp-Cp)oH), 4.21 (pseudo-t, J = 1.8 Hz, 4H, (Cp-Cp)oH), 4.06 (pseudo-t, J = 1.8 Hz, 4H, (Cp Cp)m H), 3.89 (pseudo t, J = 1.8 Hz, 4H, (Cp-Cp) mH), 3.77 (t, J = 2.0 Hz, 4H, (CpTc) oH). 13 { 1 H}NMR (100MHz, CDCl3, 298K): δ (ppm) 160.3 (2C, C=O), 134.0 (2C, ThioC-H), 133.3 (2C,ThioC-CO2Fc),132.8(2C,ThioC-H),127.8(2C,ThioC-H),116.2(2C,CpC-O) ,85.3(4C,CpC-CCp),69.2(4C,(Cp-Cp)mCH),69.0(4C,(Cp-Cp)oCH),67.5(4C,(C p-Cp)mCH), 67.3 (4C, (Cp-Cp)oCH), 64.4 (4C, (CpTc)oCH), 61.8 (4C, (CpTc)mCH). MS ES+: m / z 805.9641 ([M]+ calcd: 805.9634).

[0242] Ferrocene iodide

[0243] To a solution of ferrocene (21.3 g, 114 mmol, 1 eq.) in anhydrous degassed hexane (200 mL) was added tetramethylethylenediamine (TMEDA) (37.7 mL, 251 mmol, 2.2 eq.) and the mixture was cooled to 0°C. A bottle of nBuLi (2.5 M in hexane, 100 mL, 2.2 eq.) was added to the cold solution via cannula, and the mixture was slowly warmed to room temperature and stirred overnight. The solution was cooled to -78°C, and a separate solution of iodine (43.5 g, 171 mmol, 1.5 eq.) was prepared in diethyl ether (250 mL) and then added to the cooled solution via cannula. The mixture was warmed to 0°C, water (100 mL) was added, and then filtered over sand. The resulting filtrate was washed with brine (3 x 300 mL), dried over MgSO4, and then the solvent was removed in vacuo to give a dark red slurry. Column chromatography (silica gel, hexane / toluene (6:4)) was used to separate monoferrocene, bisferrocene and triferrocene products. The monoferrocene portion was dissolved in hexane and washed (10x 0.5M FeCl3 (aqueous solution)) to remove ferrocene and iodoferrocene. The organic phase was then washed with water until the washings were colorless, then dried (MgSO4) and the solvent removed to give 1,1'-diiodoferrocene (FcI2)-CB 597F1 (2.73 g, 6.25 mmol, 6%). The bisferrocene portion was dissolved in DCM and washed (5x 0.2M FeCl3 (aqueous solution)) to remove bisferrocene and monoiodoferrocene. The organic phase was washed in water until the washings were colorless, then dried (MgSO4) and the solvent removed to give diiodobisferrocene (Fc2I2)-CB597F4+5 (1.09 g, 1.75 mmol, 2%).

[0244]

[0245] CB 597Fl

[0246] 1H NMR (400MHz, CDCl3, δ (ppm)): 4.37 (t, 4H, CpH, 3JHH = 1.9Hz), 4.18 (t, 4H, CpH, 3JHH = 1.9Hz). 13 C NMR (101 MHz, CDCl3, δ (ppm)): 77.7 (4C, CpC), 72.4 (4C, CpC), 40.4 (2C, CI). HR-MS (ESI+): calculated: 437.8065, found: 437.8054.

[0247]

[0248] CB 597F4+F5

[0249] 1H NMR (400 MHz, CDCl3, δ (ppm)): 4.36 (pseudo-t, 4H, CpH), 4.24 (pseudo-t, 4H, CpH), 4.16 (pseudo-t, 4H, CpH), 3.98 (pseudo-t, 4H, CpH). 13C NMR (101 MHz, CDCl3, δ (ppm)): 84.8 (2C, CpC), 75.9 (2C, CpC), 71.1 (4C, CpC), 70.2 (4H, CpC), 69.7 (4H, CpC), 40.9 (2C, CI). HR-MS (ESI+): calculated: 621.8040, found: 621.8026 (some triferrocene was visible from the mass spectrum, although no evidence was found in the NMR).

[0250] Ferrocenethiocarboxylate

[0251] 1,1'-Diiodoferrocene (CB 597F1) (721 mg, 1.60 mmol, 1 eq) was prepared in laboratory grade acetonitrile (30 mL) and degassed for 10 min. Copper(II) thiophenecarboxylate (1.24 g, 6.32 mmol, 3.95 eq) and 9,10-dihydroanthracene (620 mg, 3.33 mmol, 2 eq) were then added and the mixture was heated to 80 °C and left overnight. After 24 h, 1H NMR indicated that the mixture did not contain diiodoferrocene, so DCM (50 mL) was added and the green solution was allowed to cool to room temperature. The solution was filtered through celite and purified using column chromatography (silica gel, hexane→hexane / DCM (1:1)) to give the products ferrocenylthiophenecarboxylate (FcTc)-CB598F2 (29 mg, 0.091 mmol, 6%) and ferrocenylbis(thiophenecarboxylate) (FcTc2)-598F3 (109 mg, 0.249 mmol, 16%) as the corresponding fractions.

[0252]

[0253] CB 598F2

[0254] 1H NMR (400MHz, CDCl3, δ (ppm)): 7.89 (dd, 1H, CH, JHH = 3.8Hz, 1.3Hz), 7.63 (dd, 1H, CH, JHH = 5.0Hz, 1.3Hz), 7.16 ( dd, 1H, CH, JHH = 5.0Hz, 3.8Hz), 4.56 (t, 2H, CpH, 3JHH = 2.0Hz), 4.26 (s, 5H, CpH), 4.00 (t, 2H, CpH, 3JHH = 2.0Hz).

[0255]

[0256] CB 598F3

[0257] 1H NMR (400MHz, CDCl3, δ (ppm)): 7.78 (d, 2H, CH, JHH = 3.7Hz), 7.56 (d, 2H,

[0258] CH, JHH = 5.0Hz), 7.06 (t, 2H, CH, JHH = 4.3Hz), 4.68 (pseudo t, 4H, CpH), 4.10

[0259] (pseudo t, 2H, CpH).

[0260] Ferrocene formaldehyde

[0261] To a suspension of ferrocene (5.0 g, 27 mmol, 1.0 equivalent) in diethyl ether (60 mL) was added TMEDA (10.1 mL, 67.5 mmol, 2.5 equivalents), and the resulting solution was cooled to -78 ° C. nBuLi (26 mL, 64.8 mmol, 2.4 equivalents) was added to the cold solution, and the resulting solution was warmed to room temperature and stirred overnight. The solution was then cooled to -78 ° C again, dimethylformamide (6.27 mL, 81 mmol, 3.0 equivalents) was added, and the solution color darkened. Hydrochloric acid (2.5 M, 205 mL) was added, and diethyl ether was removed in vacuo. The product was extracted in DCM (100 mL x 4), washed (1x2.5 M HCl; 1x H2O) and dried (Na2SO4), and the solvent was removed in vacuo. The monocarboxylate and dicarboxylate products were separated using column chromatography (silica gel, hexane / ethyl acetate (1:1→1:3)) to give ferrocene carboxaldehyde CB 599F2 (174 mg, 0.812 mmol, 3%) and 1,1′-dicarboxylate ferrocene CB599F3 (4.60 g, 19.0 mmol, 71%).

[0262]

[0263] CB 599F2

[0264] 1H NMR (400MHz, CDCl3, δ (ppm)): 9.96 (s, 1H, HC=O), 4.80 (pseudo t, 2H, CpH),

[0265] 4.61 (pseudo-t, 2H, CpH), 4.28 (s, 5H, CpH). 13C NMR (101 MHz, CDCl3, δ (ppm)): 193-7 (C=O), 73.4 (CpC), 69.8 (CpC). HR-MS (ESI+): calculated: 215.0159, found: 215.0168.

[0266]

[0267] CB 599F3

[0268] 1H NMR (400 MHz, CDCl3, δ (ppm)): 9.94 (s, 2H, HC=O), 4.88 (pseudo-t, 4H, CpH), 4.67 (pseudo-t, 4H, CpH). 13C NMR (101 MHz, CDCl3, δ (ppm)): 193.0 (C=O), 80.4 (CpC), 74.3 (CpC), 71.0 (CpC). HR-MS (ESI+): Calculated: 243.0108, Found: 243.0102.

[0269] Thienylferrocene

[0270] Single substitution preference

[0271] To a suspension of aluminum chloride (717 mg, 5.38 mmol, 2.0 equiv) in DCM (15 mL) was added 2-thiophenecarbonyl chloride (575 μL, 5.38 mmol, 2.0 equiv) followed by ferrocene (500 mg, 2.69 mmol, 1.0 equiv) where the orange solution turned dark blue. After stirring at room temperature for 1 hour, the mixture was poured onto ice and stirred for 30 minutes until completely melted. NaOH (25% aqueous solution) was added until neutralization was achieved and the product was then extracted in DCM (3 x 75 mL), dried (Na2SO4) and the solvent removed in vacuo to give a dark red oil. Purification was achieved using column chromatography (silica gel, hexane / ethyl acetate (95:5→50:50 gradient) to give (thienyl)ferrocene CB 601F1 (569 mg, 1.92 mmol, 71%) and 1,1′-bis(thienyl)ferrocene (2a) CB 601F2 (combined with CB 604F3-F4 and purified again to give 137 mg of product (CB 601+604) (69 g, 0.17 mmol, 6%).

[0272] Double substitution preference

[0273] To a suspension of aluminum chloride (3.58 g, 26.9 mmol, 5.0 equiv) in DCM (40 mL) was added 2-thiophenecarbonyl chloride (2.88 mL, 26.9 mmol, 5.0 equiv) followed by ferrocene (1 g, 5.38 mmol, 1.0 equiv) where the orange solution turned dark blue. After stirring overnight at room temperature, the mixture was poured onto ice and stirred for 30 minutes until completely melted. NaOH (25% aqueous solution) was added until neutralization was achieved and the product was then extracted in DCM (3 x 75 mL), dried (Na2SO4) and the solvent removed in vacuo to give a dark red oil. Purification was achieved using column chromatography (silica gel, hexane / ethyl acetate (95:5→50:50 gradient) to give 1,1′-bis(thienyl)ferrocene (2a) CB 608F5 (1.20 g, 2.95 mmol, 55%). CB 608F5 may benefit from further purification by adding another column.

[0274]

[0275] CB601F1

[0276] 1H NMR (400MHz, CDCl3, δ (ppm)): 7.93 (dd, 1H, ArH, JHH = 3.8Hz, 1.2Hz), 7.62 (dd, 1H, ArH, JHH = 4.9Hz, 1.2 Hz), 7.16 (m, 1H, ArH), 5.03 (t, 2H, CpH, 3JHH = 2.0Hz), 4.60 (t, 2H, CpH, 3JHH = 2.0Hz), 4.23 (s, 5H, CpH). 13C NMR (126MHz, CDCl3, δ (ppm)): 189.7 (C=O), 167.0 ((O=C)C), 131.9 (ArC), 131.8 (ArC), 127.8 (ArC), 72.5 (CpC), 71.1 (CpC), 70.5 (CpC). HR-MS (ESI+): calculated value: 297.0033, found value: 297.0037.

[0277]

[0278] CB 601F2

[0279] 1H NMR (400MHz, CDCl3, δ (ppm)): 7.84 (d, 2H, ArH, J HH =3.8Hz),7.63(d,2H,ArH,J HH =4.9Hz),7.13(t,2H,ArH,J HH=4.3 Hz), 5.06 (pseudo t, 4H, CpH), 4.60 (pseudo t, 4H, CpH). 13 C NMR (101 MHz, CDCl3, δ (ppm)): 188.4 (C=O), 143.9 (ArC), 132.7 (ArC), 132.2 (ArC), 128.0 (ArC), 80.5 (CpC), 74.8 (CpC), 72.8 (CpC). HR-MS (ESI+): Calculated: 406.9848, Found: 406.9863.

[0280] (Furyl)ferrocene

[0281] To a suspension of aluminum chloride (1.79 g, 13.44 mmol, 5.0 equiv) in DCM (20 mL) was added 2-furoyl chloride (1.33 mL, 13.44 mmol, 5.0 equiv) followed by ferrocene (500 mg, 2.69 mmol, 1.0 equiv) where the orange solution turned dark blue. After stirring overnight at room temperature, the mixture was poured onto ice and stirred for 30 minutes until completely melted. NaOH (25% aqueous solution) was added until neutralization was achieved and the product was then extracted in DCM (3 x 75 mL), dried (Na2SO4) and the solvent removed in vacuo to give a dark red oil. Purification was achieved using column chromatography (silica gel, hexane / ethyl acetate (95:5→50:50 gradient) to give 1,3-bis(furanyl)ferrocene CB 605F3 (90 mg, 0.32 mmol, 12%) and 1,1′-bis(furanyl)ferrocene (2b) CB 605F5 (198 mg, 0.53 mmol, 20%).

[0282] Might benefit from another column, some minor impurities present.

[0283]

[0284] CB 605F3

[0285] 1H NMR (400MHz, CDCl3, δ (ppm)): 7.76 (s, 1H, ArH), 7.65 (dd, 2H, ArH, JHH = 5.8Hz, 3.7Hz), 7.40 (d, 1H, ArH, JH H=3.7Hz), 6.69(s,1H,ArH), 5.28(t,1H,CpH,JHH=2.0Hz), 4.71(t,2H,CpH,JHH=2.0Hz), 4.23(s,5H,CpH). 13C NMR (101MHz, CDCl3, δ (ppm)): 147.3 (ArC), 120.4 (ArC), 120.3 (ArC), 117.0 (ArC), 113.0 (ArC), 73-5 (CpC), 71.3 (CpC), 70.6 (CpC). HR-MS (ESI+): calculated value: 375.0320, found value: 375.0324.

[0286]

[0287] CB 605F5

[0288] 1H NMR (400MHz, CDCl3, δ (ppm)): 7.55 (s, 2H, ArH), 7.26 (s, 2H, ArH), 6.54 (s, 2H, ArH), 5.16 (pseudo-t, 4H, CpH), 4.57 (pseudo-t, 4H, CpH). 13C NMR (101MHz, CDCl3, δ (ppm)): 145.8 (ArC), 117.3 (ArC), 112.3 (ArC), 74.4 (CpC), 72.6 (CpC). HR-MS (ESI+): Calculated value: 375.0320, Found value: 375.0335.

[0289] (Benzoyl)ferrocene

[0290] Benzoyl chloride (1.56 mL, 13.44 mmol, 5.0 equiv) was added to a suspension of aluminum chloride (1.79 g, 13.44 mmol, 5.0 equiv) in DCM (20 mL), followed by ferrocene (500 mg, 2.69 mmol, 1.0 equiv), where the orange solution turned dark blue. After stirring overnight at room temperature, the mixture was poured onto ice and stirred for 30 minutes until completely melted. NaOH (25% aqueous solution) was added until neutralization was achieved, and the product was then extracted in DCM (3 x 75 mL), dried (Na2SO4), and the solvent removed in vacuo to give a dark red oil. Purification was achieved using column chromatography (silica gel, hexane / ethyl acetate (95:5→50:50 gradient) to give 1,1'-bis(benzoyl)ferrocene(2d)CB 606F3 (745 mg, 1.89 mmol, 70%).

[0291]

[0292] CB 606F5

[0293] 1H NMR (400MHz, CDCl3, δ (ppm)): 7.78 (d, 4H, ArH, JHH = 7.6Hz), 7.54 (t, 2H, ArH, JHH = 7.5Hz), 7.42 (t, 4H, ArH, JHH = 7.6Hz), 4.91 (pseudo t, 4H, CpH), 4.58 (pseudo t, 4H, CpH). 13C NMR (101MHz, CDCl3, δ (ppm)): 197.9 (C = O), 139.3 (ArC), 132.1 (ArC), 128.5 (ArC), 128.3 (ArC), 79.6 (CpC), 74.8 (CpC), 73.3 (CpC). HR-MS (ESI+): calculated value: 395.0730, found value: 395.0734.

[0294] Exemplary Solar Cells—General Approach

[0295] The solar cells were prepared according to the following method:

[0296] Glass / ITO substrate (10~45Ωsq -1 ) were ultrasonically cleaned with detergent, deionized water, acetone and isopropanol for 5 to 30 minutes respectively.

[0297] The glass / ITO substrates were then dried in an oven at 80-120 °C, treated with oxygen plasma for 5-40 min, and finally transferred to a N2-filled glove box before use.

[0298] Prepare a concentration of 0.6 to 4.1 mg mL in a solvent-1 15-65 μL of the prepared PTAA solution was spin-coated onto the ITO substrate at 3500-700 rpm for 18-50 seconds, and then the substrate was annealed at 75-130° C. for 5-20 minutes.

[0299] A 1.2-2.2 M perovskite precursor solution was prepared by mixing CsI, FAI, MABr, PbI2, and PbBr2 in 1 mL of DMF:DMSO (3-15:1 / v:v) mixed solvent to obtain a perovskite precursor solution with the chemical formula Cs X (FA y MA 1-y ) 1-x Pb(I Z Br 1-z )3 perovskite, wherein x=(0~0.95), y=(0~1), z=(0~1), includes 3~15mol% PbI2 in excess relative to FAI.

[0300] · Then add 9.2-36.0 mol% MACl to the perovskite precursor solution and stir for 0.5-12 hours. Spin coat 30-100 μL of the perovskite solution onto the glass / ITO / HTL at 350-1800 rpm for 5-20 seconds, followed by spin coating at 3500-7000 rpm for 30-60 seconds.

[0301] 5-18 seconds before the end of spin coating, slowly drop 150-300 μL of solvent onto the center of the membrane.

[0302] The prepared perovskite film was then annealed on a hot plate at 90-150°C for 10-60 minutes.

[0303] To form the interfacial layer:

[0304] Prepare FcTc2 powder and dissolve it in solvent at a concentration of 0.3-2.2 mg mL -1 .

[0305] The prepared light yellow solution was stirred at room temperature (20-25°C) until the solution became clear. The solution was then transferred to a N2-filled glove box before use.

[0306] 60-180 μL of FcTc2 solution was spin coated on top of the prepared perovskite at 4000-6000 rpm for 10-25 seconds, then transferred to a hot plate and annealed at 85-135°C for 1-10 minutes. The spin coating process was performed at room temperature (20-25°C) in a N2-filled glove box with O2 and H2O contents <10 ppm.

[0307] To complete the device:

[0308] 4~10nm in high vacuum (<4x 10 -6 Support) 10~30nm C60 is thermally evaporated at a rate of 1.

[0309] In high vacuum (<4x 10 -6 Under the condition of 0.2~1.2A s -1 Thermal evaporation of BCP at a rate of

[0310] In high vacuum (<4x 10 -6 Support) Thermally evaporate 70-120nm silver electrode at a rate of .

[0311] Figure 3A A schematic diagram of a solar cell 300 according to this embodiment is shown.

[0312] Solar cell embodiment 1

[0313] The perovskite composition Cs was prepared according to the following general method 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3 solar cells.

[0314] Glass / ITO substrate (15Ωsq -1 ) were ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol for 20 min each.

[0315] The glass / ITO substrates were then dried in an oven at 100 °C, followed by oxygen plasma treatment for 10 min, and finally transferred to a N2-filled glove box before use.

[0316] Prepare a 2.2 mg mL -1 35 μL of the prepared PTAA solution was spin-coated onto the ITO substrate at 6000 rpm for 30 s, and then the substrate was annealed at 100 °C for 10 min.

[0317] A 1.73 M perovskite precursor solution was prepared by mixing CsI, FAI, MABr, PbI2 (5 mol% excess relative to FAI), and PbBr2 in 1 mL of DMF:DMSO (5:1 / v:v) mixed solvent to obtain a 1.73 M perovskite precursor solution having the chemical formula Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.95 Br 0.02)3. Then 15.5 mol% MACl was added to the perovskite precursor solution and stirred for 2 hours.

[0318] • 60 μL of the perovskite solution was spin coated onto the glass / ITO / HTL at 1000 rpm for 10 seconds, followed by 5000 rpm for 40 seconds.

[0319] 12 seconds before the end of spin coating, slowly drop 250 μL of CB onto the center of the membrane.

[0320] The prepared perovskite film was then annealed on a hot plate at 110 °C for 20 minutes.

[0321] To form the interfacial layer:

[0322] For Fc-treated (FcTc2, Fc2Tc2, and Fc2Tc2) devices, prepare the Fc compound and dissolve it in CB at a concentration of 1 mg mL -1 When other concentrations are used, this should be stated.

[0323] The prepared light yellow solution was stirred at room temperature (20-25°C) until the solution became clear. The solution was then transferred to a N2 filled glove box before use.

[0324] 100 μL of FcTc2 solution was spin coated on top of the prepared perovskite at 5000 rpm for 20 sec, then transferred to a hot plate and annealed at 100 °C for 2 min.

[0325] The spin coating process was carried out at room temperature (20-25°C) in a N2-filled glove box with O2 and H2O contents <10 ppm.

[0326] To complete the device:

[0327] In high vacuum (<4x 10 -6 Support) 20nm C60 was thermally evaporated at a rate of .

[0328] In high vacuum (<4x 10 -6 Support) 6nm BCP was thermally evaporated at a rate of .

[0329] In high vacuum (<4x 10 -6 Support) A 100nm silver electrode was thermally evaporated at a rate of .

[0330] The device area was defined and characterized by a metal shadow mask to 0.08 cm 2 .

[0331] The same procedure was used to form cells with an interfacial layer of Fc2Tc2 or Fc3Tc2.

[0332] Comparison of solar cells 1

[0333] A solar cell was formed as described in Solar Cell Example 1, but without the interfacial layer.

[0334] The performances of Solar Cell Example 1 and Comparative Solar Cell 1 were compared.

[0335] Experimental parameters and measurements

[0336] The device performance was characterized according to the following methods:

[0337] - XRD data were collected at room temperature in reflection mode on a Philips X'Pert diffractometer equipped with a CPS180 detector using monochromatic Cu-Ka (λ=1.5418 Å) radiation.

[0338] The surface and cross-sectional morphologies of the perovskite films were obtained by SEM (QUATTROS, Thermal Fisher Scientific).

[0339] • XPS measurements were performed with an AXIS Supra XPS system. KPFM data were acquired via a Bruker Dimension Kelvin probe force microscopy performed in a potential channel equipped with a PFQNE-AL probe.

[0340] AFM-based characterization (AFM, KPFM, and EFM) was performed by Bruker Dimension ICON under ambient conditions, and Ti / Ir-coated silicon tips (ASYELELC-01-R2) with a resonance frequency of ~58-97 KHz were used in Scanning Kelvin Probe Microscopy (SKPM) and Electrostatic Force Microscopy (EFM) imaging.

[0341] PTIR measurements were performed using a commercial Bruker NanoIR2-FS device (measurement range 900 to 1800 cm -1 ) was performed using a setup consisting of an AFM microscope operated in contact mode.

[0342] FTIR spectroscopy was performed using a Fourier transform infrared spectrometer (Tensor 27, Bruker, Germany).

[0343] Steady-state and time-resolved PL spectra were obtained using an Edinburgh FLS980 using an excitation wavelength of 485 nm.

[0344] The film thickness of perovskite was obtained by DektakXT stylus profiler.

[0345] • UV-vis absorption was measured by a UV-vis spectrometer (PerkinElmer model Lambda 2S).

[0346] • ToF-SIMS measurements were performed using a TOF-SIMS V instrument (IONTOF GmbH, Cameca IMS 4F).

[0347] The J-V characteristics of the photovoltaic devices were performed at room temperature in a N2-filled glove box by using a xenon lamp solar simulator (Enlitech, SS-F5, Taiwan, China). The power of the light was calibrated to 100 mW cm by a silicon reference cell (with a KG2 filter). -2 Before the JV measurement, a 120 nm thick magnesium fluoride layer was deposited on the back side of the ITO substrate to enhance the transmittance. All devices were measured using a Keithley 2400 source meter in the scan mode of reverse scan (1.20 V to −0.01 V) and forward scan (−0.01 V to 1.20 V), with a scan rate of 0.01 V s -1 , and the delay time is 10ms. No pre-processing is required before measurement. The active area is defined and characterized as a small area of ​​0.0414cm by a metal shadow mask. 2 and centimeter area 1.00cm 2 The stable power output is performed by monitoring the stable current density output (extracted from the reverse sweep JV curve) under the maximum power point (MPP) bias.

[0348] EQE measurements were performed by a QE-R EQE system (Enlitech, Taiwan, China). High-sensitivity EQE was measured by an integrated system (PECT-600, Enlitech, Taiwan, China), in which the photocurrent was amplified and modulated by a lock-in instrument.

[0349] The electroluminescence (EL) quantum efficiency (EQE) was measured by applying an external voltage / current source using an instrument (ELCT-3010, Enlitech, Taiwan, China). EL ).

[0350] Recorded on a Bruker Avance 400MHz spectrometer 1 H and 13 C{ 1 H} NMR spectra and referenced to residual solvent peaks at 7.26 and 77.2 ppm CDCl3 or 5.32 or 54.0 ppm CD2Cl2, respectively. 1H-NMR spectra were assigned entirely using 2D correlation spectroscopy.

[0351] The coupling constant is measured in Hz.

[0352] For peak force infrared (PFIR) imaging, a Bruker NanoIR2-FS device operated in contact mode (test range 900 to 1800 cm -1 ), the atomic force microscope (AFM) was operated in peak force tapping mode, allowing the tip-sample distance to be known during operation. During IR image acquisition, the IR source wavelength was fixed at 1480 cm -1 , the AFM tip is scanned across the sample surface, producing a chemical map with high spatial resolution, while providing high-quality IR spectra and chemical imaging for organic components in perovskite films. A phase-locked loop synchronizes the laser pulses with each peak force tapping cycle. A four-quadrant photodiode reads and digitizes the vertical deflection produced by the laser-induced contact resonance. The PFIR signal is obtained from the amplitude of the fast Fourier transform of the contact resonance. For the PFIR image, the scan area is 10x10μm2 and the scan rate is 0.5Hz. The resonant frequency of the AFM tip is 264kHz. The laser output power depends on this selected frequency.

[0353] As described herein, device stability was tested according to the following method:

[0354] · At room temperature, the long-term operation stability of the PVSC was carried out by applying the PVSC under a 1-sun equivalent LED lamp in a N2-filled glove box (where the content of O2 and H2O is <10ppm). The PVSC was biased at the maximum power point (MPP) voltage, and the PCE was measured with the MPP tracking routine using a multipotentiostat (CHI1040C, CH Instruments, Inc.). The device was kept at 25°C using a cooling system. During the MPP test, the current density-voltage (JV) curve of the device was obtained every 12 hours to obtain the appropriate load of the MPP.

[0355] Thermal stabilization was performed by applying the PVSC on a hotplate (HS 7, IKA) maintained at 85 °C in a N2-filled glove box (where the contents of O2 and H2O were <10 ppm), and the PCE evolution of the device was obtained by regular JV measurements.

[0356] • Water and oxygen stability tests were performed by applying the PVSC in ambient air (40-50% RH) without any light, and the PCE evolution of the device was obtained by regular JV measurements.

[0357] For density functional theory (DFT) calculations, the geometry optimization and frequencies of the ground states of FcTc2, Fc2Tc2, and FC3TC2 molecules were performed using the Gaussian16 package (version C01) with the B3LYP functional in combination with the 6-31g(d,p) basis set. The intramolecular electrostatic interactions were described by DFT-D3 (Grimme 2006). Electrostatic potential (ESP) analysis was performed using the MULTIWFN software. The van der Waals (vdW) isosurfaces were set equal to 0.001e / bohr 3 .

[0358] For stability testing in accordance with IEC61215:2016, PVSC is made of polyisobutylene (PIB) based polymer (PVS ) package and covered with 1.1 mm glass sheets on both sides of the device.

[0359] The damp heat test was performed by keeping the packaged devices at 85°C / 85% RH for 1000 hours in an environmental test chamber (EL-10KA, ESPEC, Japan).

[0360] For the temperature cycling test, the PVSC was placed in an environmental test chamber (EL-04KA, ESPEC) and the temperature was cycled between -40 ± 2 ° C and 85 ± 2 ° C. The temperature change rate between -40 ° C and 85 ° C was set to no more than 100 ° C / h, and the temperature was kept stable at the temperature points of -40 ° C and 85 ° C for at least 15 minutes.

[0361] result

[0362] Figure 3B Scanning electron microscope images of the different layers of Solar Cell Example 1 are shown.

[0363] Figure 3C Time-of-flight secondary ion mass spectrometry (ToF-SIMS) data are shown, which indicate that most of the FcTc2 (see Fe +The traces of () are located on the surface of the perovskite film, between the ETL 106 and the perovskite layer 110. FcTc2 is deposited on the perovskite film at a stage where perovskite crystallization has been completed. In addition, in theory, the FcTc2 molecule is too large to be incorporated into the perovskite lattice. In the ToF-SIMS data, the presence of the Fe signal in the perovskite bulk is because the specific ion signal does not disappear suddenly, but gradually weakens (the same signal tailing can also be seen for Ag, Pb, etc.). X-ray diffraction (XRD), top-view SEM and UV-vis absorption spectroscopy measurements were performed to study the crystallinity, morphology and light absorption of the perovskite films with and without FcTc2 treatment. All samples showed no obvious changes between the control device and the device with the functional layer 108, indicating that the FcTc2 compound does not affect the crystallization and light collection properties of the perovskite film.

[0364] To investigate how FcTc2 interacts with perovskite, X-ray photoelectron spectroscopy (XPS) measurements were performed. The results are shown in Figure 4. The Pb 4f ( Figure 4A )、I 3d( Figure 4B ) and N1s( Figure 4C ) The binding energies of the core energy levels are slightly shifted to higher values. This indicates that the binding of anions and cations on the perovskite surface is enhanced (this may be due to the strong binding between the surface ions and the FcTc2 interface layer 108). Fig.23 and 24 This combination is discussed further.

[0365] To investigate the effect of FcTc2 on the electrical properties of the perovskite film, Kelvin probe force microscopy (KPFM) measurements were performed to detect the surface potential of the film. The results are shown in FIG5 .

[0366] Compared with the control sample ( Figure 5A ), perovskite film functionalized by FcTc2 ( Figure 5B ) exhibits a reduced contact potential (about 50 mV), indicating direct interaction and surface charge transfer between the FcTc2 interface layer 108 and the perovskite layer 110. In addition, the FcTc2 functionalized perovskite exhibits a potential distribution (~150 mV) with a smaller surface potential difference than the control sample (~250 mV). The uniform distribution of the surface contact potential is conducive to efficient charge carrier extraction and non-radiative recombination suppression at the perovskite grain boundaries.

[0367] Time-resolved photoluminescence (TRPL) spectra were measured to evaluate the non-radiative recombination of the perovskite films, and the results of the fitting parameters are shown in Figure 6 The TRPL profile was fitted with a double exponential decay with fast and slow components based on the following equation:

[0368] τ avg =(A1τ1 2 +A2τ2 2 ) / (A1τ1+A2τ2),

[0369] Wherein the parameters A1 and A2 are the amplitude fractions of each decay component, τ1 and τ2 represent the time constants of two decays: τ1 is the time constant of the fast decay component (related to the charge trapping process), and τ2 is the time constant of the slow decay component (related to the charge detrapping or carrier recombination process).

[0370] With the incorporation of FcTc2, the carrier lifetime increased significantly from 1166.74 ns to 2159.22 ns (see also Table 1 below). The carrier lifetime is defined as the average time required for minority carriers to recombine. The increased carrier lifetime seen in Table 1 is consistent with Figure 7 The enhanced steady-state PL intensity shown in Figure 7 The results show that there is no interfacial layer and the interfacial layer has 0.5 mg mL -1 The FcTc2 concentration in the interface layer was 1.0 mg mL -1 The FcTc2 concentration and interface layer had 2.0 mg mL -1 These results indicate that the level of non-radiative recombination is reduced in the device including the interfacial layer 108, which may be due to the reduction of defects on the perovskite surface.

[0371] Table 1

[0372]

[0373] Table 2 shows the photovoltaic parameters of the best performing PSCs modified with different concentrations of Fc2Tc2.

[0374] Table 2

[0375]

[0376] In trication mixed halide perovskites, chemically reactive species such as MA at the surface of the perovskite layer 110 + and I - To estimate the effect of FcTc2 on the stability of perovskite, the MA of control and FcTc2-functionalized perovskite films were probed by peak force infrared (PFIR) microscopy under irradiation and heating conditions. + The PFIR spectrum shows that the MA in solar cell embodiment 1 + The intensity and distribution of the cations remain good after aging for 1000 hours (see Fig. 8Aand 8B ), while the comparative solar cell 1 shows a significant decrease in the intensity of the MA signal and a broadening of the distribution ( Figure 8C and 8D ). These results suggest that in the absence of an interfacial layer, ion migration and volatilization are more likely to occur, leading to increased surface defects that affect the operational stability of perovskite devices. However, FcTc2 can anchor surface ions and reduce migration, resulting in a more uniform and stable distribution of surface components.

[0377] Fig. 9 The current density-voltage (JV) curves of the solar cell embodiment 1 and the comparative solar cell 1 under AM 1.5G simulated sunlight irradiation are shown, wherein the concentration of FcTc2 is optimized to 1.0 mg mL -1 To obtain the best performance (see the comparative experimental results in Table 3 below).

[0378] Table 3

[0379]

[0380] like Fig. 9 As shown, the comparative solar cell 1 exhibits a maximum PCE of 23.02%, where the open circuit voltage (V oc ) is 1.133V, the short-circuit current density (J sc ) is 25.25 mA cm -2 , and the fill factor (FF) is 80.45%. Solar cell Example 1 exhibits an enhanced PCE of 25.03%, with an increased Voc of 1.184 V and a Jsc of 25.68 mA / cm 2 , and FF is 82.32%. Solar cell Example 1 also exhibits low hysteresis. The corresponding external quantum efficiency (EQE) spectrum (eg Fig.10 ) yields an integrated Jsc that differs slightly from the value obtained from the JV measurement. Solar cell Example 1 was also measured at the maximum power point (MPP) to obtain a stable photocurrent of 23.70 mA cm-2 and a stable PCE of 24.17%.

[0381] One of the best performing devices having the structure of Solar Cell Example 1 was verified by an independent solar cell certification laboratory (China Institute of Metrology), where a PCE of 24.3% (with Voc = 1.179 V, Jsc = 25.59 mA cm) was confirmed. -2 , and FF = 80.60%). This is the highest certified efficiency among all inverted PVSCs to date. Fig.11PCE measurements (under AM 1.5G simulated sunlight illumination) are also provided in the figure, which shows a histogram of PCE values ​​for 30 devices with and without an interfacial layer. The PCE measurements show good reproducibility, with the average PCEs of Comparative Solar Cell 1 and Solar Cell Example 1 being 22.52% and 24.47%, respectively.

[0382] In addition, according to the detailed equilibrium theory, the photovoltage loss (Voc loss) of the comparative solar cell 1 and the solar cell example 1 was quantitatively analyzed. From the electroluminescence (EL) spectrum, an EQE of 1.5% of the control device was obtained. EL and EQE of 7.0% of Solar Cell Example 1 EL , resulting in ΔV3 (Voc loss from non-radiative recombination) of 108.57 and 68.75 mV, respectively. This shows that FcTc2 as an interface modifier can significantly inhibit non-radiative recombination. The values ​​of the three components of Voc loss (ΔV1, ΔV2, ΔV3) are calculated according to Appendix 1, and the calculated values ​​are summarized in Table 4. The Voc loss of 363 mV is one of the lowest values ​​in the inverted PVSC.

[0383] Table 4

[0384]

[0385] Fig.25 The electrostatic potential distribution of different Fc compounds was shown by density functional theory (DFT) simulation. The oxygen atoms in the carboxylate end groups on each functionalized Fc compound exhibited the strongest negative electrostatic potential, which can preferentially interact with the cations in the perovskite structure. In addition, the electrostatic potentials of the carboxylate units of FcTc2, Fc2Tc2, and Fc3Tc2 were -29.79, -29.17, and -30.50 kcal mol, respectively. -1 The difference in electrostatic potential is related to the conformation of the molecule, and the relatively small electrostatic potential value of Fc2Tc2 at the carboxylate unit may be due to its most balanced molecular conformation. Although different numbers of Fc units slightly affect the electrostatic strength of different systems, they do not change the overall electrostatic distribution and the interaction between perovskite and Fc-based compounds.

[0386] The interaction between the functionalized Fc compounds and the perovskite surface was investigated using X-ray photoelectron spectroscopy (XPS). Fig.25 c and d, 31, 32). The binding energies of the Pb 4f and I 3d core levels of the Fc-treated perovskite film are slightly shifted to higher energy levels than those of the control film, indicating a change in the electronegativity on the perovskite surface, which demonstrates the interaction between the functionalized Fc compound and the uncoordinated sites on the perovskite surface. In addition, Fig.33 , 34UV-vis absorption spectra and atomic force microscopy (AFM) images in Figure 3 indicate that the interaction has no effect on the optical properties and morphology of the perovskite film.

[0387] To understand the influence of organometallic motifs, e.g. Fig.25 c shows the estimated valence evolution of Fc by XPS. The Fe2p orbital spectrum shows that the iron center exists in the Fe 3+ state and Fe 2+ In the state, 2p 3 / 2 and 2p 3 / 2 The binding energies of 1 / 2 723eV) and 708eV(2p 1 / 2 In addition, as the number of Fc units increases, Fe 3+ / Fe 2+ The ratio of α to α decreased, which means that the Fc compound bound to the surface of the perovskite film is redox-limited. This change is consistent with the previously reported valence changes of ferrocene or cobaltocene and may be attributed to the iodine anions released due to chemical damage to the perovskite crystal surface as counterions to the oxidized Fc cations.

[0388] To gain a deeper understanding of the charge transfer between the functionalized Fc compounds and the perovskite, electrostatic force microscopy (EFM) ( Fig.25 f, 25g, 35), which provides direct information about the carrier type and concentration.

[0389] EFM provides a powerful tool for discovering direct charge transfer in hybrid electronic systems. In the EFM test protocol, a bias voltage (-3 to 3 V with a step size of 1.5 V) is applied to the tip of the probe to extract the Coulomb force. Figures 1f and 1g show the phase shift profiles of the entire scan area at different bias voltages, integrated in one image for comparison. By counting the data in Figures 1f and 1g, the statistics of the phase angles at different bias voltages are shown in Fig.34 and 35 In addition, the statistical average is shown as a parabola fit in Figure 1h. A negative shift in the symmetry axis of the fitted parabola indicates the negative charge induced at the surface point or area.

[0390] Pristine and Fc2Tc2-treated membranes are representative and are shown in Fig.25 f and 25g, and which shows the integrated phase shift spectrum across the entire scan area at various bias voltages (-3V to 3V), where the corresponding phase angle statistics are shown in Fig.36 and 37 Both pristine and Fc-treated perovskite films exhibit easily discernible phase shifts. Fig.25h, the negative shift of the symmetry axis of the fitted parabola corresponds to the negative charge generated at the sample surface. 31 For the Fc-modified perovskite, the number of negative charges rises because some Fc species have been ionized due to their high electron delocalization. This indicates that electrons are transferred from the Fc compound to the perovskite surface, resulting in charge redistribution on the perovskite surface.

[0391] Surface treatment of perovskite films can tune the work function and carrier concentration. Kelvin probe force microscopy (KPFM) is used to determine the surface potential of perovskite films. Contact potential difference (CPD) images of pristine and Fc-treated perovskite films are shown in Fig.26 a to 26d. Compared with the original film, the Fc-modified perovskite film exhibits a gradually increasing CPD value with the increase of Fc units, which is attributed to the interfacial charge transfer. In addition, with the introduction of more Fc units, the Fc-modified perovskite film shows a stable growth uniformity of the surface potential ( Fig.26 e). The reduced surface potential difference can not only reduce the interface non-radiative recombination losses, but also accelerate and homogenize the charge extraction efficiency.

[0392] Furthermore, the surface work functions of the perovskite films modified with different Fc compounds were determined by calibrating the work function with Au reference. Fig.26 e to 26h, the pristine perovskite film yields a work function of 4.74 ± 0.07 eV. Surface treatment via Fc compounds results in a negative shift in the work function, and increasing the number of Fc units results in a more negative shift, leading to a value of 4.46 ± 0.02 eV for the Fc3Tc2-modified perovskite film, a change of about 300 meV. Furthermore, the change in work function occurs only within the surface layer of the perovskite film, because according to Fig.38 From the TOF-SIMS results in Figure 2, the Fc compound only binds to the perovskite surface.

[0393] To verify how surface treatment affects interfacial charge extraction and recombination, steady-state and time-resolved photoluminescence (PL and TRPL) were first performed on perovskite / ETL films (with the structure of glass / perovskite / C60). Fig.26 i and Fig.39 In the figure, the functionalized Fc treated perovskite film showed a significant decrease in PL intensity compared to the control. In addition, the carrier lifetime via the fitted TRPL spectra decreased from 189.7 ns to 33.5 ns with the increase in the number of Fc units. The decrease in PL intensity and lifetime indicates the facilitated charge extraction from the perovskite to the ETL. PL mapping was performed on the perovskite / ETL film ( Fig.40 ). The PL spectrum intensity is counted and the integral value is Fig.26j, where the x-axis is the PL spectrum intensity and the integrated area represents the PL uniformity. The control film exhibits non-uniform PL intensity, indicating an imbalance in the charge extraction efficiency. In contrast, the incorporation of Fc compounds and the optimization of Fc units to Fc2Tc2 lead to more uniform PL emission and reduced PL intensity compared to the control film, which further demonstrates that carrier extraction is accelerated and homogenized due to the introduction of Fc compounds.

[0394] In addition to charge extraction, carrier recombination and interface defect states were also investigated. First, the space charge limited current (SCLC) technique was performed on a purely electronic device. Fig.41 and 42 ) to fill the trap voltage V TFL =eN t L 2 / 2εε0 determines the trap density (N t ).

[0395] A pure electronic device with a FTO / TiO2 / perovskite / Fc / C60 / BCP / Ag structure was prepared to calculate the defect density (N). In the SCLC scheme, the current is controlled by the charge carriers injected from the contacts, and the current-voltage characteristic becomes a quadratic relationship (I~V 2 ). Fig.38 The JV curves of the fabricated devices are shown in a double logarithmic scale, which include the Ohmic region, the Trap Filling Limitation (TFL) region, and the sub-regions. In the TFL region, the trap state density (N t ) can be calculated by the following equation:

[0396]

[0397] Where s and ε0 are relative dielectric constant and vacuum dielectric constant respectively. TFL is the onset voltage of the TFL region, q is the elementary charge, and L represents the perovskite film thickness.

[0398] exist Fig.26 In k, after being functionalized by Fc compounds, the trap filling voltage gradually decreases from 0.745 V (control device) to 0.194 V (Fc2Tc2-modified device), but increases to 0.489 V for the Fc3Tc2 analog. Fig.43 A similar trend can be observed in the variation of the ideality factor (n). 34 This ideality factor decreased from 1.71 to 1.25 after the introduction of Fc2Tc2, but increased to 1.58 when surface modification was performed using Fc3Tc2. These findings demonstrate that the incorporation of functionalized Fc molecules can effectively suppress interfacial defects and carrier recombination; however, this effect is weakened when an excess of Fc units is included.

[0399] Electroluminescence (EL) measurements in the dark were performed under forward bias ( Fig.44 and 45 ). The membranes treated with Fc2Tc2 exhibited stronger emission intensity and narrower emission range compared to the control, further confirming the reduction of non-radiative recombination losses. 35 Furthermore, it is encouraging that Fig.26 k, the Fc2Tc2 modified device exhibits an EQE of 8.1% EL This is the highest value among all inverted perovskite photovoltaic devices to date. In comparison, the control device only exhibited an EQE of 3.1% under the same conditions. EL efficiency.

[0400] To investigate the effect of surface modification on PV performance, an inverted PV device was fabricated using the configuration of indium tin oxide (ITO) / poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) / perovskite / Fc molecules / C60 / 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) / silver (Ag) Fig. 27 a and 27b). Fig. 27 c and 27d show the current-voltage (JV) curves and the efficiency of PSCs with different Fc compounds. The control device exhibited a maximum PCE of 23.06%, with an open circuit voltage (V OC ) is 1.112V, the short-circuit current density (J SC ) is 25.21 mA cm -2 , and the fill factor (FF) is 82.25%. After the introduction of the Fc compound, the PSC exhibits significantly increased Voc and FF (Table 5).

[0401] Table 5: Photovoltaic parameters of the best performing PSCs modified with different functional Fc molecules.

[0402]

[0403] Compared with the control device, the Fc2Tc2-treated device produced an overall efficiency of 25.43%, with V OC 1.191V, J SC 25.47 mA cm -2 , FF is 83.82%, and the hysteresis is negligible ( Fig. 27 e and Fig.46 ). The PV performance of Fc compounds at different concentrations is summarized in Fig.47 and 48 middle.

[0404] External Quantum Efficiency (EQE) Spectrum ( Fig. 27 f) The resulting integrated JSC The value deviates only slightly from the JV measurement. The stabilized efficiency of the Fc2Tc2-modified device was also evaluated at the maximum power point (MPP), yielding 24.25 mA cm 2 The stable photocurrent and stable PCE of 25.22% ( Fig. 27 g). In addition, the devices also showed very good reproducibility with only small deviations in each PV parameter, with an average PCE of ∼22.6% for the control device and ∼25.0% for the Fc2Tc2-modified device ( Fig. 27 h). In addition, energy loss analysis showed that the non-radiative recombination losses of the control and Fc2Tc2 modified devices were 85.94 mV and 64.97 mV, respectively ( Fig.49 and 50 , Table 6), further confirming the significant contribution of Fc2Tc2 to the improvement of PSC performance.

[0405] Table 6: Key parameters of energy loss in PSCs with and without Fc2Tc2

[0406]

[0407] The long-term operational stability of the MPP encapsulated devices was examined under continuous one-sun irradiation in N2 atmosphere. Compared with the control device, the Fc2Tc2-modified device showed outstanding stability, with a PCE of more than 93% (>T93) after 4000 h ( Fig.51 ), while the control device lost more than 60% of its initial PCE after 2500 hours. The results show comparable operational stability to the FcTc2-based device ( Fig.51 ).

[0408] After confirming the outstanding small-area PV performance achieved by Fc2Tc2 modification, the inventors further fabricated large-area cells (with 1.008 cm 2 effective area) and estimated their performance. Fig.28 a shows the JV curves of the best performing large-area PSCs with and without Fc2Tc2. The control device yielded a PCE of 21.58%, with J SC 25.13mAcm -2 , V OC =1.108 V, and FF is 77.50%. In contrast, the Fc2Tc2 modified device has a lower FF (79.76%) and V OC The results show that the overall efficiency of the device is 23.77%.

[0409] In addition, Fig.28In b, the Fc2Tc2-modified device shows 23.05 mA cm-2 at a bias of 1.02 V. -2 The stable photocurrent output and stable PCE of 23.51% were achieved. Fig.28 c shows the V of 20 original devices and target devices OC Compared with the control device, the V OC and FF are higher, which is consistent with Fig.28 This is consistent with the results for the small-area device in h, indicating that the performance improvement of the large-area device also originates from the accelerated interfacial charge transfer and suppressed non-radiative recombination.

[0410] To further evaluate the PV performance uniformity of large-area devices, the inventors recorded the JV curves of our device at five separate locations, namely at the center and four corners of the device active area ( Fig.28 d). Use a 0.0414 cm 2 The square aperture area mask showed very little variation in all PV metrics of the Fc2Tc2-based devices collected from the JV curves in these five regions (Table 7).

[0411] Table 7: At 1 cm 2 Small-area photovoltaic parameters captured at different locations of the device.

[0412]

[0413] More importantly, in Fig.28 In e, the Fc2Tc2-modified device exhibits larger FF and V than the control device, based on the statistics of the small-area PV metrics captured in the large-area device. OC These results indicate that after Fc2Tc2 modification, the PV performance reaches an optimum on a square centimeter scale.

[0414] To identify the cause of the improved PV performance and uniformity, steady-state PL measurements were performed on five different regions of the perovskite / ETL film ( Fig.28 f). Fig.52 As shown, the Fc2Tc2 treated samples showed more consistent PL intensity compared to the control samples.

[0415] Normalization was performed based on the highest PL intensity in each film. Fig.28 As shown in Figure 5, the CV value of the modified film is 0.040, which is lower than that of the control film (0.893), indicating more uniform carrier extraction and transfer on a square centimeter scale. In addition, KPFM characterization is used to evaluate the surface potential changes in different regions in the perovskite film. Fig.53 and54 In the study, modification via Fc2Tc2 resulted in a more uniform surface potential at each independent region. Although the potentials at different locations deviated slightly for the control and target films, the Fc compound could reduce the potential difference at each local location, which allowed for optimal carrier extraction efficiency over a wide range of large-area perovskite devices, thus enabling scalable PSCs to achieve performance optimization at different locations.

[0416] stability

[0417] To investigate the effect of FcTc2 functionalization on device stability, the efficiency evolution under various conditions was monitored.

[0418] First, the operational stability of the unpackaged device was examined via maximum power point (MPP) tracking under continuous one-sun irradiation in N2 atmosphere. Fig.12 As shown, Solar Cell Example 1 maintains its initial efficiency within the first 200 hours and exhibits only less than 2% degradation after 1500 hours. In contrast, Comparative Solar Cell 1 drops to 72% of its initial efficiency.

[0419] In heating ( Fig.13A ) and environment ( Fig. 13B ) conditions. It can be seen that in both cases, the performance of the comparative solar cell 1 drops significantly to below 80% of the initial efficiency after 800 hours. In contrast, the device of solar cell example 1 exhibits a T98 (time to reach 98% of the initial efficiency) of 2000 hours and 1500 hours under ambient and continuous heating, respectively. Without wishing to be bound by any theory, it is possible that the chemically reactive components at the perovskite surface (such as MA) + and I - ) can be easily volatilized and migrated through light, moisture and heat degradation, and FcTc2 can enhance the stability by forming additional bonds with the perovskite surface ions and preventing any mobile ion migration.

[0420] In addition, strict stability measurements are performed in accordance with the IEC61215:2016 standard, which is the most commonly used international standard for mature photovoltaic technologies. Fig.14A As shown, the solar cell embodiment 1 device exhibited a T95 of more than 1000 hours under the damp heat test (85°C / 85% RH), and thus successfully passed the key points of the IEC61215:2016 damp heat condition compliance. Fig. 14BAs shown, under the cyclic shock of cold (-40°C) and heat (85°C), the solar cell embodiment 1 device still maintains more than 85% efficiency after 200 cycles; this is significantly better than the comparative solar cell 1 (maintaining 40% efficiency after 200 cycles). In summary, these data indicate that the FcTc2 functionalized PVSC device exhibits very promising efficiency and stability. Perovskite solar cells with such a functional interface layer have the potential to be commercialized and compete with silicon solar cells.

[0421] Solar cell embodiment 2

[0422] The MAPbI3-based device was fabricated as follows:

[0423] The procedures for ITO / glass substrate cleaning and hole transport layer (PTAA) deposition were the same as those discussed above for Solar Cell Example 1. S0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.95 Br 0.02 )3 base devices are manufactured in accordance with each other.

[0424] MAPbI3 precursor solution was prepared by mixing 1.55 M MAI and 1.63 M PbI2 in 1 mL DMF:DMSO (5:1 / v:v) mixed solvent and stirred for 2 h before use.

[0425] • 60 μL of the perovskite solution was spin coated onto the glass / ITO / HTL at 2000 rpm for 10 seconds followed by 6000 rpm for 30 seconds.

[0426] 7 seconds before the end of spin coating, 250 μL of CB was slowly dropped onto the center of the film. The prepared perovskite film was then annealed on a hot plate at 100 °C for 30 minutes.

[0427] The procedures for FcTc2 interface layer deposition and metal electrode evaporation were as described in Solar Cell Example 1.

[0428] Solar cell embodiment 3

[0429] The FAPbI3-based device was fabricated as follows:

[0430] The procedures of ITO / glass substrate cleaning and hole transport layer (PTAA) deposition were the same as those of Solar Cell Example 1.

[0431] The FAPbI3 precursor solution was prepared by mixing 2 M FAI and 2.06 M PbI2 in 1 mL DMF:DMSO (8:1 / v:v) mixed solvent. Then 35 mol% MACl was added to the perovskite precursor solution and stirred for 2 h.

[0432] • 60 μL of the perovskite solution was spin coated onto the glass / ITO / HTL at 6000 rpm for 40 seconds.

[0433] • 25 seconds before the end of spin coating, 250 μL of CB was slowly dropped onto the center of the film. The prepared perovskite film was then annealed on a hot plate at 135 °C for 1 hour.

[0434] The procedures for FcTc2 interface layer deposition and metal electrode evaporation were as described in Solar Cell Example 1.

[0435] Solar cell embodiment 4

[0436] Cs was prepared as follows 0.05 (FA 0.85 MA 0.15 ) 0.95 Pb(I 0.85 Br 0.15 )3 base devices:

[0437] The procedures of ITO / glass substrate cleaning and hole transport layer (PTAA) deposition were as described in Device Example 1.

[0438] A 1.5 M perovskite precursor solution was prepared by mixing CsI, FAI, MABr, PbI2 (10 mol% excess relative to FAI), and PbBr2 in 1 mL of DMF:DMSO (5:1 / v:v) mixed solvent, with the chemical formula C S0.05 (FA 0.85 MA 0.15 ) 0.95 Pb(I 0.85 Br 0.15 )3.

[0439] 60 μL of perovskite solution was spin coated onto glass / ITO / HTL at 5000 rpm for 30 seconds. 250 μL of CB was slowly dropped onto the center of the film 7 seconds before the end of spin coating. The prepared perovskite film was then annealed on a hot plate at 100°C for 30 minutes.

[0440] The procedures for FcTc2 interface layer deposition and metal electrode evaporation were as described in Device Example 1.

[0441] Comparison of solar cells 2-4

[0442] Comparative solar cells 2-4 were prepared as described in Solar Cell Examples 2-4, respectively, except that the FcTc2 layer was omitted.

[0443] Table 8 shows the increase in PCE for each of Comparative Devices 2-4 when the FcTc2 interface layer was included.

[0444] Table 8

[0445]

[0446]

[0447] refer to Fig.15 , 16 The benefit of the interface can be further seen in Figures 1 and 17, which compare the performance of different perovskite compositions with and without the FcTc2 interface layer.

[0448] Fig.15 A shows the JV curve of the best performing PVSC of solar cell example 2, and Fig.15 B shows a histogram of the measured PCE values ​​of 20 solar cell Example 2 devices.

[0449] Fig.16 A shows the JV curve of the best performing solar cell Example 4 device, and Fig.16 B shows a histogram of the measured PCE values ​​of 20 solar cell Example 2 devices.

[0450] Fig.17 A shows the JV curve of the best performing solar cell Example 3 device, and Fig.17 B shows a histogram of the measured PCE values ​​of 20 solar cell Example 3 devices.

[0451] Solar cell embodiment 5

[0452] A "pure electronic" solar cell device is manufactured, wherein the structure is: glass substrate (102) / FTO+TiO2 (contact 114) / perovskite layer (110) / interface layer FcTc2 (108) / C60 (ETL 106) / BCP / Ag contact 104 (according to Figure 1B 3, omitting the hole transport layer 112 and using FTO+TiO2 instead of ITO).

[0453] Comparison of solar cells 5

[0454] Comparative Solar Cell 5 was prepared as described in Solar Cell Example 5, but the FcTc2 interface layer was omitted.

[0455] Fig.18 18A and 18B show the space charge limited current (SCLC) measurement of the solar cell embodiment 5 and the comparative solar cell 5, respectively. It can be seen that when the interfacial layer 108 of the solar cell embodiment 5 is present, the trap filling limit voltage (V TFL ) after which the current density increases even more.

[0456] It can be obtained by equation N t =2εε0V TEL / eL 2 The trap filling limiting voltage is applied to calculate the trap density, where e is the elementary charge, ε is the relative permittivity of the perovskite, ε0 is the vacuum permittivity, L represents the thickness of the perovskite layer, and N t is the trap density of the perovskite film.

[0457] The calculated trap densities of the comparative solar cell 5 and the solar cell embodiment 5 are 2.76×10 15 and 8.27×10 14 , indicating that the presence of FcTc2-modified perovskite film reduces the trap density level.

[0458] like Fig.18 As shown in A and 18B, according to SCLC measurements, the carrier mobility in the “pure electron” device is increased from 2.72×10-4 cm in the comparative solar cell 5 to 2 V -1 s -1 Enhanced to 5.52×10-4cm of FcTc2 modified solar cell Example 5 2 V -1 s -1 Assuming that all layers except the interface layer in Comparative Solar Cell 5 and Solar Cell Example 5 are identical, this enhanced carrier mobility can be attributed to faster electron transfer caused by the FcTc2-modified interface.

[0459] like Fig.18 As shown in Figure C, the carrier lifetime at the perovskite / ETL interface of solar cell example 5 is shorter than the carrier lifetime at the pristine perovskite / ETL interface of comparative solar cell 5, which further indicates that electron extraction is accelerated via FcTc2.

[0460] Due to the use of organic interface materials (e.g. Fig. 20 DPC in or Fig.21 BA in Figure 2 did not demonstrate a similar improvement in interfacial carrier transport and extraction, so we can infer that the Fc moiety provides an improvement in interfacial carrier dynamics here. Therefore, without wishing to be bound by theory, it can be concluded that the use of a metallocene interfacial layer promotes electron transfer at the perovskite / ETL interface.

[0461] Comparison of solar cells 6

[0462] A solar cell was prepared as described in Solar Cell Example 1, except that a ferrocenyl-based material, ferrocenylbisphenyl (FcPh2), was used as the interface material. The molecular structure of FcPh2 is inserted in Fig.19 In B.

[0463] from Fig.19 B can be seen, compared with no interlayer Fig.19 Compared with the control device of A, the short circuit current Jsc and fill factor FF of the interface layer 108 of FcPh2 are increased. However, the FcPh2-modified PVSC does not show a significant PCE enhancement compared with the control. Without wishing to be bound by any theory, this may be due to the fact that neither the phenyl or ferrocene units can bind or interact with the perovskite and therefore cannot replace the role of the carboxylate of FcTc2 for defect passivation and carrier transport.

[0464] Comparison of solar cells 7

[0465] A solar cell was prepared as described in Solar Cell Example 1, except that diphenylcarboxylate (DPC) was used as the interface material. The molecular structure of DPC is inserted in Fig. 20 In B.

[0466] refer to Fig. 20 B, it can be seen that compared with the Fig. 20 The short-circuit current J of the DPC-modified PVSC is lower than that of the control device A. SC Without wishing to be bound by any theory, this may be due to the poor conductivity of the organic DPC interfacial layer leading to an electron transport barrier at the perovskite / ETL interface.

[0467] Comparison of solar cells 8

[0468] A solar cell was prepared as described in Solar Cell Example 1, except that butyl acetate (BA) with a high boiling point was used as the interface material as a representative ester. The molecular structure of BA is inserted in Fig.21 In B.

[0469] refer to Fig.21 B, it can be seen that compared with the Fig.21 The short-circuit current J of the BA-modified PVSC is higher than that of the control device A. SC Without wishing to be bound by any theory, this may be due to the poor conductivity of the organic BA interfacial layer leading to an electron transport barrier at the perovskite / ETL interface.

[0470] Density functional theory (DFT) simulations and electrostatic potential (ESP) analysis

[0471] Density functional theory (DFT) simulations were performed to study the interaction between the perovskite surface and the FcTc2 molecules. The (001) PbI2-terminated perovskite surface was chosen as a model because it has been shown to be stable in the lowest energy configuration. Starting from the ordered interface, enhanced bonding of O from FcTc2 to Pb from the perovskite surface was observed within a few picoseconds ( Fig.23 A and 23B, see bond length L PB-O With the interface rearrangement, the molecular dynamics reaches a stable equilibrium state, where the Pb-O bond length is simulated as (See Fig.23 C).

[0472] like Fig.24 As shown, electrostatic potential (ESP) analysis of FcTc2 indicated that the electronegativity of O in FcTc2 was high (-29.79 kcal mol-1) (the electronegativity of O, S and H atoms were -29.79 kcal mol-1, -1 、-8.12kcal mol -1 and 15.16 kcal mol -1 ). This further supports the formation of strong Pb-O bonds between the perovskite surface and FcTc2.

[0473] Regarding the XPS analysis discussed in Figure 4, combined with Fig.23 DFT simulation and Fig.24 ESP analysis indicates that there is a strong interaction between perovskite and FcTc2, which is beneficial to the passivation of surface defects and the stabilization of surface components in perovskite. Fig.23 These DFT simulations show that FcTc2 molecules can bond to uncoordinated Pb defects on the perovskite surface via Pb-O binding or bonding. This interaction between FcTc2 and perovskite (as well as strong Pb-O binding or bonding) can reduce the trap state density and suppress non-radiative recombination, an effect that is reflected by the extended carrier lifetime derived from TRPL spectra (Table 1 and Figure 6 ) and the reduced defect density calculated from the SCLC curve (see Fig.18 ) is proved.

[0474] In summary, the realization of highly efficient perovskite solar cells can be attributed, at least in part, to the following effects discussed in this paper:

[0475] (i) Interface defect passivation. The interface layer 108 (such as FcTc2) can bond to the uncoordinated Pb defects on the perovskite surface via, for example, Pb-O bonding to reduce the trap state density and suppress non-radiative recombination (see Fig.23 , 24 );

[0476] (ii) Electron transport and extraction acceleration. The fast electron transfer properties of metallocenes (such as ferrocene in FcTc2) can accelerate electron transport and extraction at the perovskite / ETL interface, which is not possible in insulating organic interface materials (see Fig. 20 and 21 );and

[0477] (iii) Improved structural compatibility and molecular flexibility. The application of FcTc2, especially its thiophene-carboxylate sidearms (which may provide O and S atoms), to modify the perovskite interface achieves better structural compatibility. Compared with conventional rigid inorganic materials, FcTc2 has better molecular flexibility and can interact more strongly with the perovskite and transport layer interfaces.

[0478] Funding Statement

[0479] This invention was supported by the ECS Fund (21301319), the Natural Science Foundation of Guangdong Province (2019A1515010761), and the Sir Edward Frankland BP Faculty Endowment Fund of Imperial College London.

[0480] Appendix 1: Photovoltage loss (V OC,loss )calculate

[0481] Detailed V OC,loss It can be described by the formula listed below:

[0482]

[0483] Where q, ΔV, E g are the basic charge, total voltage loss and band gap of the perovskite, respectively. OC SQ is the Shockley–Queisser limit of the open circuit voltage, V OC rad is the V in the PSC where no non-radiative recombination occurs OC , ΔV OC SQ V is caused by non-ideal EQE above the bandgap OC Loss, ΔV OC rad V is caused by sub-bandgap radiative recombination OC loss, and ΔV OC non-rad It is non-radiative recombination V OC loss.

[0484] Therefore, the energy loss can be divided into three parts, namely ΔV1, ΔV2 and ΔV3, which are respectively: E g The above radiative recombination, energy loss from blackbody radiation and voltage loss caused by non-radiative recombination.

[0485] By locating the Gaussian-like derivative The maximum point (λ g ), and the photovoltaic band gap (E) of 1.548 eV was obtained from the inflection point of the EQE spectrum. g,PV ) (for Comparative Solar Cell 1 and Solar Cell Example 1). For example, E g,PV is defined as the average peak energy at the absorption edge of the distribution, and it should be considered a convention for determining the bandgap energy of any solar cell. Because it represents an external property of the photovoltaic device, rather than an internal property of the photovoltaic material, using the average peak energy can enable a more accurate estimate of the bandgap of a solar cell device.

[0486] According to previous reports, the V OC It can be calculated by the following formula:

[0487]

[0488] where q, k B , T, J SC J and J0 represent element charge, Boltzmann constant, temperature, short-circuit current and dark saturation current respectively. SC and J0 can be described as:

[0489]

[0490] EQE PV ,EQE EL They are the photovoltaic external quantum efficiency and the electroluminescence external quantum efficiency. AM.5 , Φ BB are the solar cell radiation spectrum and the blackbody radiation spectrum respectively, and c is the speed of light in a vacuum.

[0491] According to the Shockley-Queisser limit (SQ limit):

[0492] (1)EQE PV It is described by the Heaviside step function, where

[0493]

[0494] (2) Only when the energy is greater than the band gap (E g ) photons are absorbed;

[0495] (3) All recombination is radiative (EQE EL =1).

[0496] Therefore, J in the SQ limit SC and J0 can be written as:

[0497]

[0498] Therefore, V in the SQ limit OC for:

[0499]

[0500] Considering the SQ limit theory, the VSQ OC can be degraded to V with three loss components: OC .

[0501] First V OC The loss component is due to the imperfect EQE PV , which is less than 100%. In this case, the short-circuit current is expressed as:

[0502]

[0503] ΔVSQ OC is calculated as follows:

[0504]

[0505] Second V OC The loss component comes from the energy loss associated with the additional thermal radiation of the solar cell in the dark. PV Extending into the sub-bandgap region, in which blackbody radiation increases as the light energy decreases. Therefore, the sub-bandgap EQE PV Increased dark saturation current. Short circuit current Jrad OC is equal to J SC , and the dark saturation current in this case can be written as:

[0506]

[0507] Therefore, the radiation V OC The loss ΔVrad OC is:

[0508]

[0509] Third V OC The loss component ΔVnonrad OC is due to non-radiative recombination in the device and can be calculated as:

[0510]

[0511] According to equation 4 and equation 11, Jrad 0 = EQE EL J0, so combining this with Equation 2, it can be seen that Equation 13 above can be rewritten as:

[0512]

[0513] Solar Cell Example 1 and Comparative Solar Cell 1 exhibited similar ΔV1 of ˜274 mV.

[0514] like Fig.44 As shown, the PSCs with and without Fc2Tc2 exhibited a ΔV1 of ∼274 mV, indicating that the radiative recombination after surface treatment was not altered. g The region below the band gap brings more black body radiation, so the high sensitivity EQE below the band gap can be characterized to calculate ΔV2. The ΔV2 calculated for solar cell embodiment 1 and comparative solar cell 1 are 20.67 mV and 31.50 mV, respectively.

[0515] ΔV3 is V from non-radiative recombination OC loss, which can be derived using Equation S22, where EQE EL is the EQE of electroluminescence (EL). ΔV3 of comparative solar cell 1 and solar cell example 1 can be calculated to be 108.57 and 68.75 mV, respectively. This result further confirms that the functional Fc molecule plays a role in accelerating interfacial charge transfer and reducing non-radiative recombination.

[0516] The external ideality factor (n) can be calculated based on qV OC =E g -nkTln(I o / I) extraction, where I o is the normalization factor, T is the absolute temperature, I is the incident light intensity, q is the elementary charge, and E g is the band gap, k is the Boltzmann constant, and T is the absolute temperature. In general, Fig.39 In , ideality factor 1 is associated with bimolecular bond-bond radiative recombination of carriers or dominant Shockley-Read-Hall (SRH) trap-assisted recombination with a pinned charge carrier density, while ideality factor 2 is associated with controlled SRH recombination without pinning a charge carrier density.

Claims

1. A photovoltaic cell comprising: a first electrode; a second electrode; a perovskite layer and an electron transport layer disposed between the first and second electrodes; as well as An interface layer is disposed between the perovskite layer and the electron transport layer and directly contacts the perovskite layer, wherein the interface layer comprises an interface compound, wherein the interface compound comprises at least one substituent R 1 Substituted metallocene, the substituent R 1 Contains at least one of O, S, N or P atoms.

2. The photovoltaic cell according to claim 1, wherein the interfacial compound is a compound of formula (I): [Metallocene]p (I) in: A metallocene is a metallocene group comprising a metallocene radical bonded to two aromatic or heteroaromatic groups Ar 1 of metal; p is at least 1; and At least one metallocene is substituted with at least one substituent R 1 replace.

3. The photovoltaic cell according to claim 2, wherein the compound of formula (I) has formula (Ia): in: M is a metal ion; Ar 1 is a monocyclic or polycyclic aromatic or heteroaromatic group at each occurrence; M and the two Ar 1 The group forms the metallocene; At least one Ar 1 By at least one R 1 replace; R 2 is a group that satisfies the valence of M; q is 0 or a positive integer; and R 3 is independently at each occurrence H or a substituent.

4. The photovoltaic cell according to any one of the preceding claims, wherein the metallocene is ferrocene.

5. A photovoltaic cell according to any one of the preceding claims, wherein R 1 is a group of formula (II): -AB (II) wherein A is a divalent group containing O, S, N or P; and B is H, C 1-12 alkyl, optionally substituted aryl, or optionally substituted heteroaryl.

6. The photovoltaic cell according to claim 5, wherein A is selected from the group consisting of: -(R 5 ) f -Z-(R 5 )g- (III) -(R 6 O) j - (IV) in: R 5 is independently at each occurrence a hydrocarbyl group; f and g are each independently 0 or 1; R 6 It is C 1-4 Alkylene, preferably ethylene; j is 1-10; as well as Z is O, S, COO, C(=S)O, C(=O)S, CONR 4 , CSNR 4 、OC(=O)O、OC(=O)NR 4 、OC(=O)PR 4 NR 4 , PR 4 ,-OP(=O)(OR 4 )-O-、-NR 4 -P(=O)(NR 4 2)-NR 4 -, where R 4 is H, optionally substituted C 1-12 alkyl or optionally substituted phenyl.

7. The photovoltaic cell according to claim 5 or 6, wherein A is -OC(=O)-.

8. The photovoltaic cell according to any one of claims 5 to 7, wherein B is selected from optionally substituted phenyl and optionally substituted 5-membered heteroaryl comprising one or more ring atoms selected from O, S and N.

9. The photovoltaic cell according to any one of claims 5 to 8, wherein B is an optionally substituted thiophene.

10. The photovoltaic cell according to any one of the preceding claims, wherein the perovskite layer comprises a perovskite of formula CatPbX3 or CatSnX3, wherein Cat is a metal cation, an organic cation or a combination thereof, and X is selected from at least one of I, Br and Cl.

11. The photovoltaic cell of any preceding claim, wherein the electron transport layer comprises fullerenes.

12. A photovoltaic module comprising a plurality of photovoltaic cells according to any one of the preceding claims, the photovoltaic cells being connected in series.

13. A compound of formula (I): [Metallocene]p (I) in: A metallocene is a metallocene group comprising a metallocene radical bonded to two aromatic or heteroaromatic groups Ar 1 of metal; p is at least 1; as well as At least one metallocene is substituted with at least one substituent R 1 Substitution, where R 1 is a group of formula (II): -AB (II) wherein A is a divalent group comprising O, S, N or P; and B is optionally substituted aryl or optionally substituted heteroaryl.

14. The compound according to claim 13, wherein Ar 1 is optionally substituted cyclopentadienyl.

15. The compound of claim 13, wherein the metallocene is ferrocene.

16. A compound according to any one of claims 13 to 15, wherein A is selected from a group of the formula: -(R 5 ) f -Z-(R 5 )g-(III) -(R 6 O) j -(IV) in: R 5 is independently at each occurrence a hydrocarbyl group; f and g are each independently 0 or 1; R 6 It is C 1-4 Alkylene, preferably ethylene; j is 1-10; as well as Z is O, S, COO, C(=S)O, C(=O)S, CONR 4 , CSNR 4 、OC(=O)O、OC(=O)NR 4 、OC(=O)PR 4 NR 4 , PR 4 ,-OP(=O)(OR 4 )-O-、-NR 4 -P(=O)(NR 4 2)-NR 4 -, where R 4 is H, optionally substituted C 1-12 alkyl or optionally substituted phenyl. The compound according to claim 16 , wherein A is —OC(═O)—.

18. A compound according to any one of claims 13 to 16, wherein B is selected from optionally substituted phenyl and optionally substituted 5-membered heteroaryl comprising one or more ring atoms selected from O, S and N.

19. The compound of claim 18, wherein B is optionally substituted thiophene.

Citation Information

Patent Citations

  • Photovoltaic device comprising a metal halide perovskite and a passivating agent

    WO2015092397A1

  • Insulating tunneling contact for efficient and stable perovskite solar cells

    WO2017160955A1

  • Contact passivation for perovskite optoelectronics

    WO2018137048A1

Cited By

  • Additive and use method thereof

    CN115843190A